GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Impacts of Culture Technique and Estuarine Position on Oyster Mariculture-mediated Nitrogen Removal in Temperate Estuaries - Nicholas P. Funnell; Suzanne P. Thompson; Chelsea M. Brown; F. Joel Fodrie; Michael F. Piehler (Estuaries and Coasts, 2026)

Correction: The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Oral Language Skills of Children and Adolescents with Neurofibromatosis Type 1: a Systematic Review and Meta-analysis - Liyan Yu; Dan Liu; Jonathan M. Payne; Heather L. Thompson; Xian Wu; Julia Moreira; Lauren Morey; Michael Peper; Hannah Iroff; Benjamin F. Mujica; Yang Hou (Neuropsychology Review, 2026)

Time in the city: long-term urban exposure predicts greater exploration and problem solving in wild red foxes - F. Blake Morton; Dylan Thompson-Jones; Kristy A. Adaway; Koko M. Sutter; Catia Matos; Georgia B. Freer; Georgia A.A. Fletcher; Carl D. Soulsbury (Animal Behaviour, 2026)

Predictors of bisphenol A exposure in pregnant women of the Barwon Infant Study - Eva J. Sugeng; Sarah Thomson; James Hedley; Martin O’Hely; Christos Symeonides; Samantha L. Dawson; Luba Sominsky; Mimi L.K. Tang; Richard Saffery; Kristie Thompson; Jochen F. Mueller; Anne-Louise Ponsonby (Toxicology Letters, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The green gap framework: Understanding non and low use of urban greenspaces - Avril Johnstone; Rob Bushby; Ruth F Hunter; Sarah Rodgers; Catharine Ward Thompson; Andrew J Williams; Benedict W Wheeler; Richard Mitchell (Landscape and Urban Planning, 2026)

Source-dependent effects of dietary astaxanthins on health and mucosal immunity in Atlantic salmon (Salmo salar) - S.M.Majharul Islam; Mette Sørensen; Gabriel Ossenkamp; Muhammad A.B. Siddik; Monica F. Brinchmann; Jørgen Lerfall; Viviane Verlhac-Trichet; Florence Perera Willora; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2026)

The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Dynamic integration of water quality simulation into Pywr - A.R. Slaughter; S. Lazar; J.E. Tomlinson; F. Thompson; N. Griffin; O.N. Odume (Environmental Modelling & Software, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Correction: Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R. Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

Sharing the cost? Soldier investment following colony fusion in basal termites - R. F. B. Padget; F. J. Thompson; R. A. Johnstone; M. A. Cant; B. Kuijper (Insectes Sociaux, 2026)
In most cooperative animal societies, interactions between groups are hostile or antagonistic. However, in a few species, groups that encounter each other can fuse together to form a new functional collective. In some ants and termites, such fusion events can be followed by changes in investment in soldiers and reproductives, for reasons that are poorly understood. Here we use a theoretical model to investigate optimal allocation to soldiers following colony fusion. Each colony can invest a proportion of its membership into the soldier caste, which provides a public benefit for the whole two-colony collective but comes at a cost to the investing colony by limiting colony growth and therefore reproduction. Our model predicts that soldier investment will typically decrease following colony fusion. However, the reported post-fusion soldier investment from empirical studies could be explained if the cost of soldier production falls following fusion. The model predicts that a colony’s reproductive output will typically decline as a result of fusion, unless the other colony makes a greater investment, or the cost of soldiers decreases sufficiently. Finally, our model predicts that smaller colonies will produce fewer soldiers than larger colonies after fusion because their lower average relatedness to the rest of the collective makes each soldier less beneficial; this means that smaller groups might, under certain conditions, gain from fusing with larger groups. Our results demonstrate two potential pathways to the evolution of group fusion in the lower termites – exploitation of additional resources or exploitation of additional soldiers (or potentially other workers). Within-group conflict, not considered in our model, may explain some discrepancies between our model and empirical reports.

An integrated framework for early detection and transmissibility assessment of emerging variants in wastewater - Xingwen Chen; Tin Phan; Wei Lin Lee; Katie Clark; Steven F. Rhode; Samantha Brozak; Bruce Pell; Tsultrim Palden; Mats Leifels; Anna Gitter; Yang Kuang; Stefan Wuertz; et al. (International Journal of Hygiene and Environmental Health, 2026)

The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Population-specific transcriptomics of Pacific oyster after exposure to a highly pathogenic, globally distributed virus - Bernarda Calla; Neil F. Thompson; Colleen A. Burge (Fish & Shellfish Immunology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.

Household air pollution exposure is associated with perturbations in metabolic pathways in human milk: An observational untargeted metabolomics analysis from Guatemala - Jada Hoyle-Gardner; Ziyin Tang; Donghai Liang; Anaite Diaz-Artiga; Ajay Pillarisetti; Luke Naeher; Kasthuri Sivalogan; Erick Mollinedo; Jiantong Wang; Thomas F. Clasen; Lisa M. Thompson; Sheela S. Sinharoy (Environmental Research, 2026)

Examining life cycle impacts of metropolitan food system scenarios: comparing top-down and bottom-up LCA modeling approaches - Tiffanie F. Stone; Janette R. Thompson; Kurt A. Rosentrater (The International Journal of Life Cycle Assessment, 2026)
Purpose Food systems have evolved to supply the growing demands of urban populations, often without providing reliable supplies of nutritious, environmentally sustainable foods. In this study we assessed life cycle impacts (global warming potential (GWP), energy, water, and land use) for the Des Moines Metropolitan Statistical Area (DM-MSA) U.S. Midwest) food system, comparing two LCA modeling approaches. Methods Metropolitan food system scenarios for the DM-MSA include a baseline in which about 95% of table food is imported, compared to an alternative where 50% of food is grown within the MSA (local scenarios). Food system environmental impacts were quantified using the Environmentally Extended Input Output (USEEIO) model (2020 to 2050) and a CleanMetrics model (2020). Results Based on outputs from both models the local food system scenarios produced consistently lower per capita environmental impacts. The local USEEIO scenario predicted 25% less water use and 15% less GWP produced and energy used compared to baseline scenarios. However, overall the USEEIO model reported more than twice the GWP produced and energy and water use per person in 2020 compared to the CleanMetrics model. Land use was calculated outside the two model frameworks and used data for regionally-specific yields in USEEIO which significantly reduced land area needed to achieve the target production. Conclusion Increased local food production could substantially lower the environmental footprint of urban food systems in the U.S. Midwest. The re-structured version of the USEEIO model also provides opportunities for integration with other social, water, energy and climate models, enabling a more holistic perspective on food system production, consumption and impacts at critical decision-making scales.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Corrigendum to “Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar)” [Aquaculture Volume 612, Part 1, 15 January 2026, 743142]. - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar) - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

Pedigree-based genome-wide imputation using a low-density amplicon panel for the highly polymorphic Pacific oyster Crassostrea (Magallana) gigas - Ben J.G. Sutherland; Konstantin Divilov; Neil F. Thompson; Thomas A. Delomas; Spencer L. Lunda; Christopher J. Langdon; Timothy J. Green (Aquaculture, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Deep neural networks and genome-wide associations reveal the polygenic architecture of local brain aging - Nicholas J. Kim; Ayati Mishra; Nahian F. Chowdhury; Samuel D. Anderson; Owen M. Vega; Nikhil N. Chaudhari; Kenneth H. Buetow; Paul M. Thompson; Andrei Irimia (GeroScience, 2025)
Local brain age (LBA) is a regional metric of brain aging that offers a spatially resolved alternative to global brain age, but whose genetic basis is unexplored. This study reports the first genome-wide association study of cortical LBA, as estimated by a deep neural network from the T 1 -weighted magnetic resonance images of 41,708 cognitively normal adults in the UK Biobank. We identified 1,212 single-nucleotide polymorphisms (SNPs) significantly associated with LBA in at least one brain region. Genes mapped to these SNPs are involved in developmental, metabolic, immune, and cytoskeletal pathways. Dimensionality reduction of SNP association profiles uncovered three clusters linked to morphogenetic, cytoskeletal, and immuno-epigenetic processes, helping to relate neuroanatomic, immunosenescent and epigenetic mechanisms of brain aging. Top variants are mapped to KCNK2 , NUAK1 , GMNC , MSL2 , and to other genes implicated in neurodevelopment and neurodegeneration. Spatial clustering of LBA-associated variants in default mode, limbic, and motor network regions parallel regional vulnerability to Alzheimer’s disease and frontotemporal dementia. These findings establish a polygenic architecture for regional brain aging and support LBA as a genetically informed phenotype for studying aging-related neurodegeneration. Our results suggest that cortical aging is not governed by isolated loci but by coordinated genetic programs—rooted in development, metabolism, and cellular structure—that confer lifelong patterns of regional brain vulnerability and resilience. This first genetic dissection of spatially specific brain aging reveals a polygenic landscape of coordinated genetic programs, developmentally encoded and metabolically maintained during senescence. This study reframes aging as an anatomically specific genetic process reflecting the varying structural vulnerabilities observed across neurodegenerative diseases.

Comparative toxicity of Karlodinium veneficum from France and New Zealand on fish gill cells and oyster gametes - Anne Rolton; Guillaume Barnouin; Hannah Greenhough; Audrey Duval; Karthiga Kumanan; Nelly Quéré Le Goïc; Lucy Thompson; Damien Réveillon; Fabienne Hervé; Andrew I. Selwood; Hélène Hégaret; Kirsty F. Smith; et al. (Harmful Algae, 2025)

Corrigendum to “Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression” [Fish Shellfish Immunol. 149 (2024) 109549] - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2025)

The benthic and epiphytic marine dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands, an updated checklist from 2018 to 2024 - Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; Sarah C. Finch; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2025)
A checklist collating records of New Zealand’s benthic and epiphytic dinoflagellate species was published on‐line in 2018 [Rhodes L, Smith KF. 2019. A checklist of the benthic and epiphytic marine dinoflagellates of New Zealand, including Rangitāhua/Kermadec Islands. N Z J Mar Freshw Res. 53:258–277. doi: 10.1080/00288330.2018.1492425 ]. Over the last six years, seventeen species from nine genera (three newly reported genera) have been documented, including sand‐dwelling species. Isolation and identification of species using traditional microscopic techniques combined with analysis of DNA sequencing data has been supplemented by high‐throughput sequencing techniques (i.e. metabarcoding). Toxin data, based on liquid chromatography mass spectrometry (LC‐MS/MS), and toxicity of isolates are included where applicable. Forty‐two benthic and epiphytic dinoflagellate genera, including genera having benthic life stages, have now been recorded in Aotearoa New Zealand coastal waters including Rangitāhua Kermadec Islands (new record genera in bold): Adenoides , Alexandrium , Amphidinium , Archaeperidinium , Azadinium , Biecheleria , Blastodinium , Bysmatrum , Cachonina , Coolia , Crypthecodinium , Cryptoperidiniopsis , Dinophysis , Durinskia , Ensiculifera , Fukuyoa , Fragilidium , Gambierdiscus , Gonyaulax , Gymnodinium , Gyrodinium , Heterocapsa , Karenia , Karlodinium , Kryptoperidinium , Lepidodinium , Ostreopsis , Pelagodinium , Pentapharsodinium , Pfiesteria , Polarella , Prorocentrum , Protodinium , Protoperidinium , Pseudadenoides , Pseudopfiesteria , Scrippsiella , Symbiodinium , Thecadinium , Togula , Vulcanodinium and Woloszynskia.

Inundation of different river bank heights influences organic matter concentrations and zooplankton abundance - James N. Hitchcock; Andrew J. Brooks; Tim Haeusler; Paul J. McInerney; Dane F. Parsons; Ross M. Thompson (Limnology and Oceanography, 2025)
Regulation and water extraction change flow regimes in lowland rivers, affecting ecosystem functions and wetting patterns of riverbanks. River connectivity to lateral environments is crucial for organic matter cycling and the life cycles of diapausing microinvertebrates. While extreme hydraulic periods (floods and cease‐flow) are well‐studied, the impact of small to medium flows on riverine carbon flux is less understood. We conducted a mesocosm study to examine litter, nutrient, and zooplankton contributions from different bank heights in the Mehi River, Australia. Sediment from three bank heights (lower, lower + middle, and lower + middle + upper) was added to 1000 L mesocosms. Upper bank heights had more organic matter, leaf litter, and live plant coverage. Sediment from upper and middle banks increased organic carbon and phosphorus concentrations. Zooplankton abundance was higher in treatments with upper bank sediment compared to lower bank sediment. Zooplankton communities varied, with rotifer taxa including Keratella valga and Filinia passa in upper bank treatments. We estimated zooplankton biomass contributions under current regulated hydrology and compared them to a predevelopment scenario without water extraction. Regulation has reduced zooplankton input from banks by about 8.8%. Inundating higher banks increases carbon and microinvertebrate availability for food webs compared to only inundating lower sections. These findings inform effective flow management strategies and highlight how targeted environmental water use can enhance lowland river ecosystem productivity.

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Performance of soy-winter wheat relay intercropping under various water conditions - Jennifer B. Thompson; Thomas F. Döring; Sonoko D. Bellingrath-Kimura; Jing Yu; Moritz Reckling (Field Crops Research, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

The Registered Dietitian's Knowledge and Confidence in Counseling Patients with Type 2 Diabetes Experiencing Anxiety, Depression and Diabetes Distress - J. Clampitt; S. Mandali; L. Thompson; F. Steger (Journal of the Academy of Nutrition and Dietetics, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Correction: Mitonuclear incompatibility as an alternative hypothesis for male-biased offspring sex ratios arising from extra-pair matings - Markus Neuhäuser; L. Scott Johnson; Brian S. Masters; Scott K. Sakaluk; Charles F. Thompson (Journal of Ornithology, 2025)

Mitonuclear incompatibility as an alternative hypothesis for male-biased offspring sex ratios arising from extra-pair matings - Markus Neuhäuser; L. Scott Johnson; Brian S. Masters; Scott K. Sakaluk; Charles F. Thompson (Journal of Ornithology, 2025)

Wildfire induced release of Cr nanoparticles from Tire Crumb Rubber - Carmen M. Villarruel; Aaron Goodman; Hark Karkee; Heather Lowers; Jay Thompson; Alexander Gundlach-Graham; James F. Ranville (Journal of Hazardous Materials, 2025)

Household air pollution exposure in adult women is associated with increased carotid intima-media thickness: A cross-sectional study of the Household Air Pollution Intervention Network trial. - Lindsay J. Underhill; Lisa de las Fuentes; Laura Nicolaou; Shakir Hossen; Anaite Diaz-Artiga; Ajay Pillarisetti; Aris T. Papageorghiou; Florien Ndagijimana; Ghislaine Rosa; Gurusamy Thangavel; John P. McCracken; Kalpana Balakrishnan; et al. (International Journal of Hygiene and Environmental Health, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Frequency and antimicrobial susceptibility profiles of bacterial species isolated from canine and feline urine samples in Sydney, Australia, 2012–2021 - Annie Y. Wei; Mary F. Thompson; Kate A. Worthing; Carola Venturini; Victoria J. Brookes; Jacqueline M. Norris (Veterinary Microbiology, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Fitness incentives to male fighters undermine fighting performance in intergroup contests - P.A. Green; D.W.E. Sankey; T. Collins; F. Mwanguhya; H.J. Nichols; M.A. Cant; F.J. Thompson (Animal Behaviour, 2025)

Development and characterization of a novel NEIL1 nanobody - Marlo K. Thompson; Mark H. Eggers; Danielle Flores; Israel Valenzuela; Zhengrong Yang; Joel F. Andrews; Tom Johnsten; Aishwarya Prakash (DNA Repair, 2025)

Sponge taxonomy in the -omics era: resolving Haplosclerida polytomies with phylogenetics and metabolomics - Camille V. Leal; André Bispo; Mirelle Takaki; Vitor F. Freire; Maggie M. Reddy; Fabiano L. Thompson; Eduardo Hajdu; Olivier P. Thomas; Roberto G.S. Berlinck (Biochemical Systematics and Ecology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Will the declining sea ice extent in the Arctic cause a reversal of net benthic-pelagic exchange directions? - Saskia Rühl; Charlotte E.L. Thompson; Ana M. Queirós; Joanne E. Hopkins; Sian F. Henley; Stephen Widdicombe (Journal of Marine Systems, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Serum concentrations of PFAS across Australian States and Territories - Sandra Nilsson; Nathaniel Kucharski; Julia Orr; Jennifer Bräunig; Kristie Thompson; Olivier Jolliet; Daman Langguth; Carl Kennedy; Peter Hobson; Kevin V. Thomas; Jochen F. Mueller; Leisa-Maree Toms (International Journal of Hygiene and Environmental Health, 2025)

Genetic Insights into Brain Morphology: a Genome-Wide Association Study of Cortical Thickness and T1-Weighted MRI Gray Matter-White Matter Intensity Contrast - Nicholas J. Kim; Nahian F. Chowdhury; Kenneth H. Buetow; Paul M. Thompson; Andrei Irimia (Neuroinformatics, 2025)
In T 1 -weighted magnetic resonance imaging (MRI), cortical thickness (CT) and gray-white matter contrast (GWC) capture brain morphological traits and vary with age-related disease. To gain insight into genetic factors underlying brain structure and dynamics observed during neurodegeneration, this genome-wide association study (GWAS) quantifies the relationship between single nucleotide polymorphisms (SNPs) and both CT and GWC in UK Biobank participants ( N = 43,002). To our knowledge, this is the first GWAS to investigate the genetic determinants of cortical T 1 -MRI GWC in humans. We found 251 SNPs associated with CT or GWC for at least 1% of cortical locations, including 42 for both CT and GWC; 127 for only CT; and 82 for only GWC. Identified SNPs include rs1080066 (THSB1, featuring the strongest association with both CT and GWC), rs13107325 (SLC39A8, linked to CT at the largest number of cortical locations), and rs864736 (KCNK2, associated with GWC at the largest number of cortical locations). Dimensionality reduction reveals three major gene ontologies constraining CT (neural signaling, ion transport, cell migration) and four constraining GWC (neural cell development, cellular homeostasis, tissue repair, ion transport). Our findings provide insight into genetic determinants of GWC and CT, highlighting pathways associated with brain anatomy and dynamics of neurodegeneration. These insights can assist the development of gene therapies and treatments targeting brain diseases.

The application of digital tools for knowledge sharing in agriculture: A longitudinal case study from four Australian grower groups - A. Ollerenshaw; H. Thompson; H. Luke; P. Cooke; F. Best; N. Scholz; D. Fear; N. Craig; J. Telfer; A. Wright; S. Kruger (Computers and Electronics in Agriculture, 2025)

Antibiotic-resistance genes and metals increase in polluted tropical rivers of the Baia da Ilha Grande, Rio de Janeiro, Brazil - Leonardo F. Bacha; Marcelo de A.P. Oliveira; Felipe Landuci; Ana Carolina Vicente; Pedro H. Paz; Michele Lima; Marcella Hilário; Lucia S. Campos; Mateus Thompson; Caroline Chueke; Diogo Tschoeke; Adacto Ottoni; et al. (Science of The Total Environment, 2025)

Separating leaf area index from plant area index using semi-supervised classification of digital hemispheric canopy photographs: A case study of dryland vegetation - Jake Eckersley; Caitlin E. Moore; Sally E. Thompson; Michael Renton; Pauline F. Grierson (Agricultural and Forest Meteorology, 2025)

Spatial arrangement of intercropping impacts natural enemy abundance and aphid predation in an intensive farming system - Jennifer B. Thompson; Thomas F. Döring; Sonoko Dorothea Bellingrath-Kimura; Kathrin Grahmann; Michael Glemnitz; Moritz Reckling (Agriculture, Ecosystems & Environment, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

Submissions of diagnostic samples of two critically endangered species of handfish ( Branchionichthys hirsutus and Thymichthys politus ) from a public aquarium from 2018 to 2024 - Barbara F. Nowak; Graeme Knowles; Judith Handlinger; Rachelle Hawkins; Khattapan Jantawongsri; Mai Dang; Andrew Thompson; Rebecca van Gelderen; Nathan J. Bott (Journal of Fish Diseases, 2025)
Handfish (Family Brachionichthyidae) is the most threatened marine teleost fish family, however, there is little information on handfish health. We reviewed the results of submissions of mortalities from captive and captive bred spotted handfish ( Branchionichthys hirsutus (Lacepède, 1804)) and red handfish ( Thymichthys politus (Richardson, 1844)) from a public aquarium from January 2018 to February 2024. Seventeen cases for spotted handfish (comprising 33 individuals) and five cases for red handfish (one individual each) were submitted for mortality investigation. In 2018–2019, six of seven cases were diagnosed with scuticociliatosis. Other conditions included epitheliocystis (1 of 17), infections with metazoan parasites (2 of 17 for spotted handfish and 2 of 5 for red handfish) and hepatic lipidosis (4 of 17). Most submissions were fixed samples for histology with only one fish suitable for microbiology. We recommend development of a coordinated health program for all captive breeders and aquaria, which should include sampling protocols, collection, and preservation in a range of fixatives of all the dying or dead handfish and adapting sublethal sampling, including tank water to assess presence of pathogens and other microorganisms. Risk factors for handfish health in captivity should be assessed. Handfish health database should be established to avoid loss of corporate knowledge in this area.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

An accuracy assessment of the surface reflectance product from the EMIT imaging spectrometer - Red Willow Coleman; David R. Thompson; Philip G. Brodrick; Eyal Ben Dor; Evan Cox; Carlos Pérez García-Pando; Todd Hoefen; Raymond F. Kokaly; John M. Meyer; Francisco Ochoa; Gregory S. Okin; Daniela Heller Pearlshtien; et al. (Remote Sensing of Environment, 2024)

Risk avoidance during dispersal: Temporal and behavioral shifts in selection by non-resident eastern wolves (Canis c.f. lycaon) - Connor A. Thompson; John F. Benson; Brent R. Patterson (Biological Conservation, 2024)

Resistance and resilience: Tidal freshwater marsh response and recovery to acute and chronic saltwater intrusion - Madeleine F. Thompson; Steve C. Pennings; Joseph P. Schubauer-Berigan; Ellen R. Herbert; Galen Costomiris; Christopher B. Craft (Estuarine, Coastal and Shelf Science, 2024)

Leveraging ecological indicators to improve short term forecasts of fish recruitment - Eric J. Ward; Mary E. Hunsicker; Kristin N. Marshall; Kiva L. Oken; Brice X. Semmens; John C. Field; Melissa A. Haltuch; Kelli F. Johnson; Ian G. Taylor; Andrew R. Thompson; Nick Tolimieri (Fish and Fisheries, 2024)
Forecasting the recruitment of fish populations with skill has been a challenge in fisheries for over a century. Previous large‐scale meta‐analyses have suggested linkages between environmental or ecosystem drivers and recruitment; however, applying this information in a management setting remains underutilized. Here, we use a well‐studied database of groundfish assessments from the West Coast of the USA to ask whether environmental variables or ecosystem indicators derived from long‐term monitoring datasets offer an improvement in our ability to skilfully forecast fish recruitment. A secondary question is which types of modelling approaches (ranging from linear models to non‐parametric methods) yield the best forecast skill. Third, we examine whether simultaneous forecasting of multiple species offers an advantage over generating species‐specific forecasts. We find that for approximately one third of the 29 assessed stocks, ecosystem indicators from juvenile surveys yields the highest out of sample predictive skill compared to other covariates (including environmental variables from Regional Ocean Modeling System output) or null models. Across modelling approaches, our results suggest that simpler linear modelling approaches do as well or better than more complicated approaches (reducing out of sample Root Mean Square Error by ~40% compared to null models), and that there appears to be little benefit to performing multispecies forecasts instead of single‐species forecasts. Our results provide a general framework for generating recruitment forecasts in other species and ecosystems, as well as a benchmark for future analyses to evaluate skill. The most promising applications are likely for species that are short lived, have relatively high recruitment variability, and moderate amounts of age or length data. Forecasts using our approach may be useful in identifying covariates or mechanisms to include in operational assessments but also provide qualitative advice to managers implementing ecosystem based fisheries management.

Cyclobutrifluram (TYMIRIUM® technology): Low risks of a soil applied nematicide and fungicide to non-target soil invertebrates and bees - Helen Thompson; F. Javier Peris-Felipo; Natalia Peranginangin; Mike Pocock; Ana Lia Gayan-Quijano (Crop Protection, 2024)

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Comparison of juvenile coral assemblages between Australia’s Coral Sea and Great Barrier Reef Marine Parks - Deborah Burn; Andrew S. Hoey; Chiara Pisapia; Josie F. Chandler; Cassandra A. Thompson; Morgan S. Pratchett (Coral Reefs, 2024)
Densities of juvenile corals (≤ 50 mm diameter) are expected to vary between geographically isolated and more spatially proximate reefs, and may constrain local recovery potential. This study compared juvenile coral densities and their relationships with local abundance of adult congenerics at geographically isolated reefs within Australia’s Coral Sea Marine Park (CSMP) versus highly connected reefs within the Great Barrier Reef Marine Park (GBRMP). Three latitudinal regions and two habitats (reef crest and slope) were examined within both marine parks to test for spatial variation. Densities of juvenile corals in the CSMP (13.99 ± 0.72 juveniles 10 m −2 ) were significantly lower compared to those in the GBRMP (23.72 ± 1.86 juveniles 10 m −2 ). Specifically, there were significantly less Acropora and Pocillopora juveniles on the reef crest in the central CSMP compared to the GBRMP. Relationships between juvenile abundance and percent coral cover were greatest for Acropora and Pocillopora in the GBRMP. This may be due to the low range of coral cover estimates recorded in the CSMP, especially for Acropora (0–15%). Low juvenile coral abundance, and in particular, the lack of fast-growing juvenile corals (e.g., Acropora ) in the Central CSMP, in combination with low cover of broodstock (particularly Acropora ) on CSMP reefs, poses a significant constraint on post-disturbance recovery capacity, possibly attributable to isolation and limited connectivity among reefs in this region.

Assessing selection potential for Pacific oyster (Crassostrea gigas) to a North American OsHV-1 μvar: Comparing two experimental assay methods - Neil F. Thompson; M. Victoria Agnew; Bernarda Calla; Colleen A. Burge (Aquaculture, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Deterioration of bio-based polylactic acid plastic teabags under environmental conditions and their associated effects on earthworms - W. Courtene-Jones; F. Burgevin; L. Munns; M.B.T. Shillam; F. De Falco; A. Buchard; R.D. Handy; R.C. Thompson; M.E. Hanley (Science of The Total Environment, 2024)

Insect meal in aquafeeds: A sustainable path to enhanced mucosal immunity in fish - S.M. Majharul Islam; Muhammad A.B. Siddik; Mette Sørensen; Monica F. Brinchmann; Kim D. Thompson; David S. Francis; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Genomic and physiological characterization of Kitasatospora sp. nov., an actinobacterium with potential for biotechnological application isolated from Cerrado soil - I. C. Cunha-Ferreira; C. S. Vizzotto; M. A. M. Freitas; J. Peixoto; L. S. Carvalho; M. R. Tótola; F. L. Thompson; R. H. Krüger (Brazilian Journal of Microbiology, 2024)

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Microhaplotypes generate higher breeding value accuracy compared to SNPs for imputation-based breeding strategies - Thomas A. Delomas; Christopher M. Hollenbeck; Joseph L. Matt; Neil F. Thompson (Aquaculture, 2024)

Sudden peak in tetrodotoxin in French oysters during the summer of 2021: Source investigation using microscopy, metabarcoding and droplet digital PCR - Laura Biessy; John K. Pearman; Kenneth Neil Mertens; Damien Réveillon; Véronique Savar; Philipp Hess; Hannah Hampton; Lucy Thompson; Luc Lebrun; Aouregan Terre-Terrillon; Kirsty F. Smith (Toxicon, 2024)

An individual-based model for direct and indirect transmission of chronic wasting disease in free-ranging white-tailed deer - Noelle E Thompson; David J Butts; Michael S Murillo; Daniel J O'Brien; Sonja A Christensen; William F Porter; Gary J Roloff (Ecological Modelling, 2024)

Genotype-by-environment interactions and local adaptation shape selection in the US National Chip Processing Trial - Husain I. Agha; Jeffrey B. Endelman; Jessica Chitwood-Brown; Mark Clough; Joseph Coombs; Walter S. De Jong; David S. Douches; Charles R. Higgins; David G. Holm; Richard Novy; Marcio F. R. Resende; Vidyasagar Sathuvalli; et al. (Theoretical and Applied Genetics, 2024)
Key message We find evidence of selection for local adaptation and extensive genotype-by-environment interaction in the potato National Chip Processing Trial (NCPT). Abstract We present a novel method for dissecting the interplay between selection, local adaptation and environmental response in plant breeding schemes. Balancing local adaptation and the desire for widely adapted cultivars is challenging for plant breeders and makes genotype-by-environment interactions (GxE) an important target of selection. Selecting for GxE requires plant breeders to evaluate plants across multiple environments. One way breeders have accomplished this is to test advanced materials across many locations. Public potato breeders test advanced breeding material in the National Chip Processing Trial (NCPT), a public–private partnership where breeders from ten institutions submit advanced chip lines to be evaluated in up to ten locations across the country. These clones are genotyped and phenotyped for important agronomic traits. We used these data to interrogate the NCPT for GxE. Further, because breeders submitting clones to the NCPT select in a relatively small geographic range for the first 3 years of selection, we examined these data for evidence of incidental selection for local adaptation, and the alleles underlying it, using an environmental genome-wide association study (envGWAS). We found genomic regions associated with continuous environmental variables and discrete breeding programs, as well as regions of the genome potentially underlying GxE for yield.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Understanding vessel noise across a network of marine protected areas - Megan F McKenna; Timothy J Rowell; Tetyana Margolina; Simone Baumann-Pickering; Alba Solsona-Berga; Jeffrey D Adams; John Joseph; Ella B Kim; Annebelle CM Kok; Anke Kügler; Marc O Lammers; Karlina Merkens; et al. (Environmental Monitoring and Assessment, 2024)
Protected areas are typically managed as a network of sites exposed to varying anthropogenic conditions. Managing these networks benefits from monitoring of conditions across sites to help prioritize coordinated efforts. Monitoring marine vessel activity and related underwater radiated noise impacts across a network of protected areas, like the U.S. National Marine Sanctuary system, helps managers ensure the quality of habitats used by a wide range of marine species. Here, we use underwater acoustic detections of vessels to quantify different characteristics of vessel noise at 25 locations within eight marine sanctuaries including the Hawaiian Archipelago and the U.S. east and west coasts. Vessel noise metrics, including temporal presence and sound levels, were paired with Automatic Identification System (AIS) vessel tracking data to derive a suite of robust vessel noise indicators for use across the network of marine protected areas. Network-wide comparisons revealed a spectrum of vessel noise conditions that closely matched AIS vessel traffic composition. Shifts in vessel noise were correlated with the decrease in vessel activity early in the COVID-19 pandemic, and vessel speed reduction management initiatives. Improving our understanding of vessel noise conditions in these protected areas can help direct opportunities for reducing vessel noise, such as establishing and maintaining noise-free periods, enhancing port efficiency, engaging with regional and international vessel quieting initiatives, and leveraging co-benefits of management actions for reducing ocean noise.

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

Features of the highway road network that generate or retain tyre wear particles - Florence N. F. Parker-Jurd; Geoffrey D. Abbott; Bill Guthery; Gustav M. C. Parker-Jurd; Richard C. Thompson (Environmental Science and Pollution Research, 2024)

Effects of a liquefied petroleum gas stove intervention on stillbirth, congenital anomalies and neonatal mortality: A multi-country household air pollution intervention network trial - Ashley Younger; Wenlu Ye; Abbey Alkon; Kristen Harknett; Miles A. Kirby; Lisa Elon; Amy E. Lovvorn; Jiantong Wang; Anaité Diaz-Artiga; John P. McCracken; Adly Castañaza Gonzalez; Libny Monroy Alarcon; et al. (Environmental Pollution, 2024)

Correction: Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Coupled luminescence and cosmogenic nuclide dating of postglacial deflation surfaces and sand drift on a raised ice-contact delta at Veinge, SW Sweden - Helena Alexanderson; Per Möller; Mayank Jain; Mads F. Knudsen; Nicolaj Krog Larsen; Zoran M. Perić; Anne Sofie Søndergaard; Warren Thompson (Quaternary Geochronology, 2024)

Polycyclic aromatic hydrocarbons in tropical Australian stalagmites: a framework for reconstructing paleofire activity - Elena Argiriadis; Rhawn F. Denniston; Stefania Ondei; David M.J.S. Bowman; Giulia Genuzio; Huong Quynh Anh Nguyen; Jamie Thompson; Mattia Baltieri; Jonathan Azenon; John Cugley; David Woods; William F. Humphreys; et al. (Geochimica et Cosmochimica Acta, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Intruding into a conversation: how behavioral manipulation could support management of Xylella fastidiosa and its insect vectors - Sabina Avosani; Rachele Nieri; Valerio Mazzoni; Gianfranco Anfora; Zeinab Hamouche; Caterina Zippari; Maria Luisa Vitale; Vincenzo Verrastro; Eustachio Tarasco; Ilaria D’Isita; Salvatore Germinara; Thomas F. Döring; et al. (Journal of Pest Science, 2024)
Behavioral manipulation (BM) is a multimodal control approach based on the interference with the stimuli mediating insect perception and interaction with the surroundings. BM could represent a win–win strategy for the management of vector-borne plant pathogens as the bacterium Xylella fastidiosa , since it could reduce the number of vectors alighting on host plants and, consequently, the chances for transmission to occur. In this review, we summarized current knowledge and highlighted gaps in information on (i) how insect vectors of X. fastidiosa in general, and more specifically the meadow spittlebug Philaenus spumarius , locate and accept the host plant ; and (ii) how behavioral manipulation techniques could be applied to disrupt the vector–host plant interaction. Finally, we discussed how diverse BM strategies could be combined with other integrated pest management tools to protect olive groves from inoculation with the fastidious bacterium.

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Song structure of male Northern House Wrens and patterns of song production and delivery across the nesting cycle - Rachael A. DiSciullo; Scott K. Sakaluk; Charles F. Thompson (Journal of Ornithology, 2024)

Simultaneous stream assessment of antibiotics, bacteria, antibiotic resistant bacteria, and antibiotic resistance genes in an agricultural region of the United States - Carrie E. Givens; Dana W. Kolpin; Laura E. Hubbard; Shannon M. Meppelink; David M. Cwiertny; Darrin A. Thompson; Rachael F. Lane; Michaelah C. Wilson (Science of The Total Environment, 2023)

Cetaceans of the Saya de Malha bank region, Indian Ocean: A candidate Important Marine Mammal Area - Thomas Webber; Tim Lewis; Sheena Talma; Shaama Sandooyea; Laura Meller; Violaine Dulau-Drouot; Kirsten F. Thompson (Regional Studies in Marine Science, 2023)

Magnesium oxide loaded mesoporous silica: Synthesis, characterisation and use in removing lead and cadmium from water supplies - Wahran M. Saod; Ian W. Oliver; David F. Thompson; Simon Holborn; Alessandro Contini; Vladimir Zholobenko (Environmental Nanotechnology, Monitoring & Management, 2023)

Diabetes Mellitus Type 2 as a Risk Factor and Outcome Modifier for Cryptococcosis in HIV Negative, Non-transplant Patients, a Propensity Score Match Analysis - Vanessa M. Kung; Carolina Ferraz; Matthew Kennis; Carlos Franco-Paredes; Jose Tuells; Lilian Vargas Barahona; Leland Shapiro; George R. Thompson; Daniel B. Chastain; Andrés F. Henao-Martínez (Current Microbiology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

The Structural Response of the Human Head to a Vertex Impact - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Andrew M. Dwyer; Nigel R. Jones; Claire F. Jones (Annals of Biomedical Engineering, 2023)
In experimental models of cervical spine trauma caused by near-vertex head-first impact, a surrogate headform may be substituted for the cadaveric head. To inform headform design and to verify that such substitution is valid, the force-deformation response of the human head with boundary conditions relevant to cervical spine head-first impact models is required. There are currently no biomechanics data that characterize the force-deformation response of the isolated head supported at the occiput and compressed at the vertex by a flat impactor. The effect of impact velocity (1, 2 or 3 m/s) on the response of human heads ( N = 22) subjected to vertex impacts, while supported by a rigid occipital mount, was investigated. 1 and 2 m/s impacts elicited force-deformation responses with two linear regions, while 3 m/s impacts resulted in a single linear region and skull base ring fractures. Peak force and stiffness increased from 1 to 2 and 3 m/s. Deformation at peak force and absorbed energy increased from 1 to 2 m/s, but decreased from 2 to 3 m/s. The data reported herein enhances the limited knowledge on the human head’s response to a vertex impact, which may allow for validation of surrogate head models in this loading scenario.

Distinct patterns of inheritance shape life‐history traits in steelhead trout - Anne K. Beulke; Alicia Abadía‐Cardoso; Devon E. Pearse; Laura C. Goetz; Neil F. Thompson; Eric C. Anderson; John Carlos Garza (Molecular Ecology, 2023)
Life‐history variation is the raw material of adaptation, and understanding its genetic and environmental underpinnings is key to designing effective conservation strategies. We used large‐scale genetic pedigree reconstruction of anadromous steelhead trout ( Oncorhynchus mykiss ) from the Russian River, CA, USA, to elucidate sex‐specific patterns of life‐history traits and their heritability. SNP data from adults returning from sea over a 14‐year period were used to identify 13,474 parent–offspring trios. These pedigrees were used to determine age structure, size distributions and family sizes for these fish, as well as to estimate the heritability of two key life‐history traits, spawn date and age at maturity (first reproduction). Spawn date was highly heritable ( h 2 = 0.73) and had a cross‐sex genetic correlation near unity. We provide the first estimate of heritability for age at maturity in ocean‐going fish from this species and found it to be highly heritable ( h 2 from 0.29 to 0.62, depending on sex and method), with a much lower genetic correlation across sexes. We also evaluated genotypes at a migration‐associated inversion polymorphism and found sex‐specific correlations with age at maturity. The significant heritability of these two key reproductive traits in these imperiled fish, and their patterns of inheritance in the two sexes, is consistent with predictions of both natural and sexually antagonistic selection (sexes experience opposing selection pressures). This emphasizes the importance of anthropogenic factors, including hatchery practices and ecosystem modifications, in shaping the fitness of this species, thus providing important guidance for management and conservation efforts.

Devaluation Effects in Food-Specific Response Inhibition Training: A Conceptual Replication - L. Tzavella; C.R. Pennington; K.S. Button; F. Abdullahi; E. Aboaba; Z. Abutayeh; N. Bushell; A. Caddle; S. Chi Chan; A. Denman; C. Gabe-Jones; M. Mushongah; et al. (Appetite, 2023)

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

Sub-tropical benthic/epiphytic dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; J. Sam Murray; Emillie M F Passfield; Roberta D'Archino; Wendy Nelson; Tomohiro Nishimura; Lucy Thompson; Tom Trnski (Harmful Algae, 2023)

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

The distribution of coastal fish eDNA sequences in the Anthropocene - Laetitia Mathon; Virginie Marques; Stéphanie Manel; Camille Albouy; Marco Andrello; Emilie Boulanger; Julie Deter; Régis Hocdé; Fabien Leprieur; Tom B. Letessier; Nicolas Loiseau; Eva Maire; et al. (Global Ecology and Biogeography, 2023)
Aim Coastal fishes have a fundamental role in marine ecosystem functioning and contributions to people, but face increasing threats due to climate change, habitat degradation and overexploitation. The extent to which human pressures are impacting coastal fish biodiversity in comparison with geographic and environmental factors at large spatial scale is still under scrutiny. Here, we took advantage of environmental DNA (eDNA) metabarcoding to investigate the relationship between fish biodiversity, including taxonomic and genetic components, and environmental but also socio‐economic factors. Location Tropical, temperate and polar coastal areas. Time period Present day. Major taxa studied Marine fishes. Methods We analysed fish eDNA in 263 stations (samples) in 68 sites distributed across polar, temperate and tropical regions. We modelled the effect of environmental, geographic and socio‐economic factors on α‐ and β‐diversity. We then computed the partial effect of each factor on several fish biodiversity components using taxonomic molecular units (MOTU) and genetic sequences. We also investigated the relationship between fish genetic α‐ and β‐diversity measured from our barcodes, and phylogenetic but also functional diversity. Results We show that fish eDNA MOTU and sequence α‐ and β‐diversity have the strongest correlation with environmental factors on coastal ecosystems worldwide. However, our models also reveal a negative correlation between biodiversity and human dependence on marine ecosystems. In areas with high dependence, diversity of all fish, cryptobenthic fish and large fish MOTUs declined steeply. Finally, we show that a sequence diversity index, accounting for genetic distance between pairs of MOTUs, within and between communities, is a reliable proxy of phylogenetic and functional diversity. Main conclusions Together, our results demonstrate that short eDNA sequences can be used to assess climate and direct human impacts on marine biodiversity at large scale in the Anthropocene and can further be extended to investigate biodiversity in its phylogenetic and functional dimensions.

Impact of the 2014–2016 marine heatwave on US and Canada West Coast fisheries: Surprises and lessons from key case studies - Christopher M. Free; Sean C. Anderson; Elizabeth A. Hellmers; Barbara A. Muhling; Michael O. Navarro; Kate Richerson; Lauren A. Rogers; William H. Satterthwaite; Andrew R. Thompson; Jenn M. Burt; Steven D. Gaines; Kristin N. Marshall; et al. (Fish and Fisheries, 2023)
Marine heatwaves are increasingly affecting marine ecosystems, with cascading impacts on coastal economies, communities, and food systems. Studies of heatwaves provide crucial insights into potential ecosystem shifts under future climate change and put fisheries social‐ecological systems through “stress tests” that expose both vulnerabilities and resilience. The 2014–16 Northeast Pacific heatwave was the strongest and longest marine heatwave on record and resulted in profound ecological changes that impacted fisheries, fisheries management, and human livelihoods. Here, we synthesize the impacts of the 2014–2016 marine heatwave on US and Canada West Coast fisheries and extract key lessons for preparing global fisheries science, management, and industries for the future. We set the stage with a brief review of the impacts of the heatwave on marine ecosystems and the first systematic analysis of the economic impacts of these changes on commercial and recreational fisheries. We then examine ten key case studies that provide instructive examples of the complex and surprising challenges that heatwaves pose to fisheries social‐ecological systems. These reveal important insights into improving the resilience of monitoring and management and increasing adaptive capacity to future stressors. Key recommendations include: (1) expanding monitoring to enhance mechanistic understanding, provide early warning signals, and improve predictions of impacts; (2) increasing the flexibility, adaptiveness, and inclusiveness of management where possible; (3) using simulation testing to help guide management decisions; and (4) enhancing the adaptive capacity of fishing communities by promoting engagement, flexibility, experimentation, and failsafes. These advancements are important as global fisheries prepare for a changing ocean.

Evaluation of chorionic girdle organoids for ultrastructure and equine Chorionic Gonadotropin production - Riley E Thompson; Mindy A Meyers; Christianne Magee; Amanda M de Mestre; Douglas F Antczak; Fiona K Hollinshead (Journal of Equine Veterinary Science, 2023)

Metagenomic characterization of the equine endometrial microbiome during anestrus - Babiche A Heil; Machteld van Heule; Sadie K Thompson; Tabitha A Kearns; Kalie F Beckers; Erin L Oberhaus; Gary King; Pouya Dini; Jennifer L Sones (Journal of Equine Veterinary Science, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

From the Lebombo Monocline to the Mozambique Deep Basin, using combined wide-angle and reflection seismic data - M. Moulin; A. Leprêtre; F. Verrier; P. Schnürle; M. Evain; P. de Clarens; J. Thompson; N. Dias; A. Afilhado; A. Loureiro; D. Aslanian (Tectonophysics, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Insights into the distribution and ingestion of prey-like plastic fishing lures in Mediterranean rough-toothed dolphins - Ilias Foskolos; Paraskevi Alexiadou; Niki Koutouzi; Silvia Frey; Kirsten F. Thompson; Oliver Boisseau; Alexandros Frantzis (Marine Pollution Bulletin, 2023)

Modeling a localized metropolitan food system in the Midwest USA: Life cycle impacts of scenarios for Des Moines, Iowa - Tiffanie F. Stone; Janette R. Thompson; Kurt A. Rosentrater; Matt Liebman (Science of The Total Environment, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Urgent assessment needed to evaluate potential impacts on cetaceans from deep seabed mining - Kirsten F. Thompson; Kathryn A. Miller; Jake Wacker; Solène Derville; Christopher Laing; David Santillo; Paul Johnston (Frontiers in Marine Science, 2023)
Deep seabed mining operations, if permitted, could present significant risks to ocean ecosystems. Disturbance on any scale is likely to be long lasting and irreversible. Scant research to date has examined the impact that deep sea minerals extraction would have on cetaceans. The Clarion-Clipperton Zone (CCZ) is of particular interest to mining companies aiming to exploit polymetallic nodules. The CCZ, with an average depth of 5,500 m and an area of approximately 11,650,000 km 2 , is a habitat for cetaceans including baleen (mysticetes) and toothed whales (odontocetes). Of particular concern is anthropogenic noise. If permitted, commercial-scale mining is expected to operate 24-hours a day, at varying depths. The sounds produced from mining operations, including from remotely operated vehicles on the seafloor, overlap with the frequencies at which cetaceans communicate, which can cause auditory masking and behavior change in marine mammals. Cetaceans are already facing numerous stressors, including climate change, and many species are still recovering from centuries of exploitation. We argue the need for urgent research to assess more fully the potential impact of deep seabed mining on cetaceans.

Publisher Correction: Development and evaluation of a bovine lung-on-chip (bLOC) to study bovine respiratory diseases - Diane F. Lee; Clare L. Thompson; Ronald E. Baynes; Hiroko Enomoto; Geof W. Smith; Mark A. Chambers (In vitro models, 2023)

‘Eye in the sky’: Off-the-shelf unmanned aerial vehicle (UAV) highlights exposure of marine turtles to floating litter (FML) in nearshore waters of Mayo Bay, Philippines - Neil Angelo S. Abreo; Remie M. Aurelio; Vladimer B. Kobayashi; Kirsten F. Thompson (Marine Pollution Bulletin, 2023)

Evaluating cost-effective genotyping strategies for genomic selection in oysters - Thomas A. Delomas; Christopher M. Hollenbeck; Joseph L. Matt; Neil F. Thompson (Aquaculture, 2023)

Seasonal and diel modulation of DOM in a mangrove-dominated estuary - L.O. Vidal; T. Lambert; L.C. Cotovicz Jr.; M.C. Bernardes; R. Sobrinho; F. Thompson; G.D. Garcia; B.A. Knoppers; P.V. Gatts; C.R. Régis; G. Abril; C.E. Rezende (Science of The Total Environment, 2023)

A Review of the Compressive Stiffness of the Human Head - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Claire F. Jones (Annals of Biomedical Engineering, 2022)
Synthetic surrogate head models are used in biomechanical studies to investigate skull, brain, and cervical spine injury. To ensure appropriate biofidelity of these head models, the stiffness is often tuned so that the surrogate’s response approximates the cadaveric response corridor. Impact parameters such as energy, and loading direction and region, can influence injury prediction measures, such as impact force and head acceleration. An improved understanding of how impact parameters affect the head’s structural response is required for designing better surrogate head models. This study comprises a synthesis and review of all existing ex vivo head stiffness data, and the primary factors that influence the force–deformation response are discussed. Eighteen studies from 1972 to 2019 were identified. Head stiffness statistically varied with age (pediatric vs. adult), loading region, and rate. The contact area of the impactor likely affects stiffness, whereas the impactor mass likely does not. The head’s response to frontal impacts was widely reported, but few studies have evaluated the response to other impact locations and directions. The findings from this review indicate that further work is required to assess the effect of head constraints, loading region, and impactor geometry, across a range of relevant scenarios.

Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2022)

Non-Native Marsh Grass (Phragmites australis) Enhances Both Storm and Ambient Nitrogen Removal Capacity in Marine Systems - Mollie R. Yacano; Suzanne P. Thompson; Michael F. Piehler (Estuaries and Coasts, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Development and evaluation of a bovine lung-on-chip (bLOC) to study bovine respiratory diseases - Diane F. Lee; Clare L. Thompson; Ronald E. Baynes; Hiroko Enomoto; Geof W. Smith; Mark A. Chambers (In vitro models, 2022)
Purpose Current air-liquid interface (ALI) models of bovine proximal airways have their limitations. They do not simulate blood flow necessary to mimic systemic drug administration, and repeated sampling requires multiple, independent cultures. A bovine lung-on-chip (bLOC) would overcome these limitations, providing a convenient and cost-effective model for pharmacokinetic or pathogenicity studies. Methods Bovine pulmonary arterial endothelial cells seeded into the endothelial channel of an Emulate Lung-Chip were interfaced with bovine bronchial epithelial cells in the epithelial channel. Cells were cultured at ALI for up to 21 days. Differentiation was assessed by mucin quantification, phase-contrast light microscopy and immunofluorescence of cell-specific markers in fixed cultures. Barrier integrity was determined by FITC-labelled dextran 3–5 kDa permeability. To evaluate the model, endothelial-epithelial transport of the antibiotic drug, danofloxacin, was followed using liquid chromatography-mass spectrometry, with the aim of replicating data previously determined in vivo. Results bLOC cultures secreted quantifiable mucins, whilst cilia formation was evident in the epithelial channel. Barrier integrity of the model was demonstrated by resistance to FITC-Dextran 3–5 kDa permeation. Bronchial epithelial and endothelial cell-specific markers were observed. Close to plasma, representative PK data for danofloxacin was observed in the endothelial channel; however, danofloxacin in the epithelial channel was mostly below the limit of quantification. Conclusion A co-culture model of the bovine proximal airway was successfully generated, with potential to replace in vivo experimentation. With further optimisation and characterisation, the bLOC may be suitable to perform drug pharmacokinetic studies for bovine respiratory disease (BRD), and other applications.

Evaluation and characterisation of metal sorption and retention by drinking water treatment residuals (WTRs) for environmental remediation - K. A. H. Arab; D. F. Thompson; I. W. Oliver (International Journal of Environmental Science and Technology, 2022)
Drinking water treatment residuals (WTRs) are wastes generated when water is clarified using aluminium or iron salts. They are increasingly being considered as a resource with potential reuse value, particularly in relation to soil or water remediation. Adsorption–desorption capacity of Al-based (Al-WTR) and Fe-based (Fe-WTR) materials was investigated here for Pb and Zn, both separately and in combination, as a preliminary trial to assess their utility for immobilising contaminant metals in environmental settings. Maximum adsorption observed at the highest test solution concentrations imposed (400 mg/L) was similar for each WTR type and each metal; Al-WTRs sorbed Zn at 3579 mg/kg and Pb at 4025 mg/kg, while Fe-WTRs sorbed Zn and Pb at 3579 mg/kg and 3980 mg/kg, respectively. Equilibrium adsorption data were tested against Langmuir, Freundlich, and Temkin isotherm models, which indicated a substantial reserve capacity for further Pb sorption and that multiple sorption mechanisms were involved. Subsequent desorption tests with 0.001 M CaCl 2 solution indicated that > 89.76% of sorbed metal remained sorbed. When in solution together, both metals were strongly sorbed by WTRs, but a slight preference for Pb was observed. The results indicate that WTRs would be very effective immobilising agents if placed in contaminated soil or if used to treat contaminated waters.

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Analyses of three‐dimensional species associations reveal departures from neutrality in a tropical forest - Jenny Zambrano; Gabriel Arellano; Nathan G. Swenson; Phillip P. A. Staniczenko; Jill Thompson; William F. Fagan (Ecology, 2022)
The study of community spatial structure is central to understanding diversity patterns over space and species co‐occurrence at local scales. Although most analytical approaches consider horizontal and vertical dimensions separately, in this study we introduce a three‐dimensional spatial analysis that simultaneously includes horizontal and vertical species associations. Using tree census data (2000–2016) and allometries from the Luquillo forest plot in Puerto Rico, we show that spatial organization becomes less random over time as the forest recovered from land‐use legacy effects and hurricane disturbance. Tree species vertical segregation is predominant in the forest with almost all species that co‐occur in the horizontal plane avoiding each other in the vertical dimension. Horizontal segregation is less common than vertical, whereas three‐dimensional aggregation (a proxy for direct tree competition) is the least frequent type of spatial association. Furthermore, dominant species are involved in more non‐random spatial associations, implying that species co‐occurrence is facilitated by species segregation in space. This novel three‐dimensional analysis allowed us to identify and quantify tree species spatial distributions, how interspecific competition was reduced through forest structure, and how it changed over time after disturbance, in ways not detectable from two‐dimensional analyses alone.

Plume Layer Influences the Amazon Reef Sponge Microbiome Primary Producers - Otávio H. B. Pinto; Till L. V. Bornemann; Rafael S. Oliveira; Tayna D. Frederico; Betania F. Quirino; Alexander J. Probst; Mayanne A. M. de Freitas; Fabiano L. Thompson; Ricardo H. Kruger (Frontiers in Marine Science, 2022)
Symbiont relationships between corals and photosynthetic microorganisms sustain coral reef existence. However, the Great Amazon Reef System (GARS) stays under a plume layer that attenuates the entry of light, and instead of corals, sponges are the major reef epifauna, for which little is known about the function of the associated microbiome. Here, we used genome-resolved metagenomics to investigate how the sponge microbiome supports its host and overcomes the reduced light availability, recovering 205 MAGs from Agelas and Geodia sponges with completeness >70% and contamination <10%. Beta diversity estimates based on the 16S rRNA genes indicated the microbiomes of Amazon and Caribbean sponges to be distinct (P<0.01), with heterotrophic lifestyles being prevalent in Amazon sponge microbiomes (P<0.05). Nevertheless, genes indicating the carbon fixation pathways 3-Hydroxypropionate/4-Hydroxybutyrate cycle, 3-Hydroxypropionate bicycle, Reductive Tricarboxylic Acid Cycle, and Calvin-Benson-Bassham cycle could be recovered in low abundance. The presence of Cyanobacteria, represented by both 16S rRNA analyses and low-quality MAGs indicated light incidence on the reef. The metabolic profile shows that the GARS sponge microbiome had genes for sulfate reduction, sulfur oxidation, nitric oxide reduction, ammonia oxidation, nitrate reduction, nitrite ammonification, nitrite oxidation, and nitrite reduction, indicating that the microbiome might play a role in detoxification of the holobiont. We conclude, that neither the plume-limited photosynthesis of the sponge microbiome nor the primary producers sustain the organic carbon input for the sponges, which likely live off plume-associated organic carbon and their heterotrophic microbiota.

The Effect of Axial Compression and Distraction on Cervical Facet Cartilage Apposition During Shear and Bending Motions - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2022)
During cervical spine trauma, complex intervertebral motions can cause a reduction in facet joint cartilage apposition area (CAA), leading to cervical facet dislocation (CFD). Intervertebral compression and distraction likely alter the magnitude and location of CAA, and may influence the risk of facet fracture. The aim of this study was to investigate facet joint CAA resulting from intervertebral distraction (2.5 mm) or compression (50, 300 N) superimposed on shear and bending motions. Intervertebral and facet joint kinematics were applied to multi rigid-body kinematic models of twelve C6/C7 motion segments (70 ± 13 year, nine male) with specimen-specific cartilage profiles. CAA was qualitatively and quantitatively compared between distraction and compression conditions for each motion; linear mixed-effects models ( α = 0.05) were applied. Distraction significantly decreased CAA throughout all motions, compared to the compressed conditions ( p

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - John Thompson; Mark A. Weaver; Ingrid Lupatsch; Robin J. Shields; Sue Plummer; Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be an approach for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio ( Listonella ) anguillarum , Vibrio alginolyticus , and V. harveyi , using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum , and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (> 100°C) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH; however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp ( Penaeus vannamei)— identified tentatively as Carnobacterium maltaromaticum . This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and reduced shrimp survival at a dose of 1 × 10 7 bacteria/shrimp. During a 28-day feeding trial, juvenile P. vannamei fed with L. plantarum supplemented diets showed no gross changes in growth parameters compared with the control. We suggest that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Beyond bulk: Density fractions explain heterogeneity in global soil carbon abundance and persistence - Katherine Heckman; Caitlin E. Hicks Pries; Corey R. Lawrence; Craig Rasmussen; Susan E. Crow; Alison M. Hoyt; Sophie F. von Fromm; Zheng Shi; Shane Stoner; Casey McGrath; Jeffrey Beem‐Miller; Asmeret Asefaw Berhe; et al. (Global Change Biology, 2022)
Understanding the controls on the amount and persistence of soil organic carbon (C) is essential for predicting its sensitivity to global change. The response may depend on whether C is unprotected, isolated within aggregates, or protected from decomposition by mineral associations. Here, we present a global synthesis of the relative influence of environmental factors on soil organic C partitioning among pools, abundance in each pool (mg C g −1 soil), and persistence (as approximated by radiocarbon abundance) in relatively unprotected particulate and protected mineral‐bound pools. We show that C within particulate and mineral‐associated pools consistently differed from one another in degree of persistence and relationship to environmental factors. Soil depth was the best predictor of C abundance and persistence, though it accounted for more variance in persistence. Persistence of all C pools decreased with increasing mean annual temperature (MAT) throughout the soil profile, whereas persistence increased with increasing wetness index (MAP/PET) in subsurface soils (30–176 cm). The relationship of C abundance (mg C g −1 soil) to climate varied among pools and with depth. Mineral‐associated C in surface soils (

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Integrating seabird dietary and groundfish stock assessment data: Can puffins predict pollock spawning stock biomass in the North Pacific? - William J. Sydeman; Sarah Ann Thompson; John F. Piatt; Stephani G. Zador; Martin W. Dorn (Fish and Fisheries, 2022)
Information on the annual variability in abundance and growth of juvenile groundfish can be useful for predicting fisheries stocks, but is often poorly known owing to difficulties in sampling fish in their first year of life. In the Western Gulf of Alaska (WGoA) and Eastern Bering Sea (EBS) ecosystems, three species of puffin (tufted and horned puffin, Fratercula cirrhata, Fratercula corniculata, and rhinoceros auklet , Cerorhinca monocerata , Alcidae), regularly prey upon (i.e., “sample”) age‐0 groundfish, including walleye pollock ( Gadus chalcogramma , Gadidae) and Pacific cod ( Gadus microcephalus , Gadidae). Here, we test the hypothesis that integrating puffin dietary data with walleye pollock stock assessment data provides information useful for fisheries management, including indices of interannual variation in age‐0 abundance and growth. To test this hypothesis, we conducted cross‐correlation and regression analyses of puffin‐based indices and spawning stock biomass (SSB) for the WGoA and EBS walleye pollock stocks. For the WGoA, SSB leads the abundance of age‐0 fish in the puffin diet, indicating that puffins sample the downstream production of the WGoA spawning stock. By contrast, the abundance and growth of age‐0 fish sampled by puffins lead SSB for the EBS stock by 1–3 years, indicating that the puffin diet proxies incoming year class strength for this stock. Our study indicates connectivity between the WGoA and EBS walleye pollock stocks. Integration of non‐traditional data sources, such as seabird diet data, with stock assessment data appears useful to inform information gaps important for managing US fisheries in the North Pacific.

Estimating Facet Joint Apposition with Specimen-Specific Computer Models of Subaxial Cervical Spine Kinematics - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2021)

Treatment with Atorvastatin During Vascular Remodeling Promotes Pericyte-Mediated Blood-Brain Barrier Maturation Following Ischemic Stroke - Yirong Yang; Lisa Y. Yang; Victor M. Salayandia; Jeffrey F. Thompson; Michel Torbey; Yi Yang (Translational Stroke Research, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Challenging the Need for Deep Seabed Mining From the Perspective of Metal Demand, Biodiversity, Ecosystems Services, and Benefit Sharing - K. A. Miller; K. Brigden; D. Santillo; D. Currie; P. Johnston; K. F. Thompson (Frontiers in Marine Science, 2021)
The extraction of minerals from the seabed of the deep oceans is of increasing interest to investors, mining companies and some coastal states. To date, no commercial-scale deep seabed mining has taken place but there is considerable pressure for minerals mining to become an economic reality, including to supply the projected demand for metals to support a global transition to renewable energy. At the same time, the full environmental impacts of deep seabed mining are difficult to predict but are expected to be highly damaging, both within, and perhaps well beyond, the areas mined. Here, we reflect on the considerable uncertainties that exist in relation to deep seabed mining. In particular, we provide a perspective on: (1) arguments that deep seabed mining is needed to supply minerals for the green energy revolution, using the electric vehicle battery industry as an illustration; (2) risks to biodiversity, ecosystem function and related ecosystem services; and (3) the lack of equitable benefit sharing to the global community now and for future generations. We explore the justification for a global moratorium on deep seabed mining to ensure protection of marine ecosystems, the need to focus on baseline research, and how improved governance of targeted marine regions could be key to the preservation and conservation of the ocean biome.

Contribution of social media to cetacean research in Southeast Asia: illuminating populations vulnerable to litter - Amber Coram; Neil Angelo S. Abreo; Robert P. Ellis; Kirsten F. Thompson (Biodiversity and Conservation, 2021)
Litter in the marine environment, in particular plastic, is a significant threat to marine megafauna. Cetaceans are known to ingest or become entangled in marine debris, likely impacting individuals and populations. Southeast Asia is a biodiversity hotspot and harbours a diverse cetacean assemblage. However, there are key knowledge gaps relating to the impact of litter in this region due the lack of experts to survey its vast coastlines. This study aims to address such gaps by using social media, gathering data from Facebook posts relating to cetacean strandings and litter across Southeast Asia between 2009 and 2019. Results show that at least 15 cetacean species have been negatively affected by litter, with ingestion most commonly affecting deep-diving species. Epipelagic and mesopelagic foragers were most vulnerable to entanglement. Davao in the Philippines was identified as a litter-related stranding hotspot. The Irrawaddy dolphin ( Orcaella brevirostris ) and pygmy sperm whale ( Kogia breviceps ) are particularly vulnerable to litter. The combination of social media and peer reviewed literature can help build a more complete picture of the spatial distribution of marine litter and the scale of the impact it has on cetacean populations. In this study we provide details of a valuable online tool for helping to understand the impact of marine litter on cetaceans and other charismatic species that are a focus of community engagement.

Microbiology of a NaCl stalactite ‘salticle’ in Triassic halite - Thomas P. Thompson; Stephen A. Kelly; Timofey Skvortsov; Gill Plunkett; Alastair Ruffell; John E. Hallsworth; Jason Hopps; Brendan F. Gilmore (Environmental Microbiology, 2021)
Summary Large regions of Earth's surface are underlain by salt deposits that evaporated from ancient oceans and are populated by extreme halophilic microbes. Some of these halophiles may have been preserved over geological timescales within hypersaline fluid inclusions, but ingresses of water and/or anthropogenic activities can lead to the formation of alternative habitats, including NaCl stalactites or other speleothems. While the microbiology of ancient evaporites has been well studied, the ecology of these recently formed structures is less‐well understood. Here, the microbiology of a NaCl stalactite (‘salticle’) in a Triassic halite mine is characterized. The specific aims were to determine the presence of fluid inclusions, determine the microbial structure of the salticle compared with a nearby brine‐pool and surficial soil, and characterize the ecophysiological capabilities of this unique ecosystem. The salticle contained fluid inclusions, and their microbiome was composed of Euryarchaetota, Proteobacteria, and Actinobacteria, with Haloarchaea in greater abundance than brine‐pool or soil microbiomes. The salticle metagenome exhibited a greater abundance of genes involved in osmoregulation, anaerobic respiration, UV resistance, oxidative stress, and stress‐protein synthesis relative to the soil microbiome. We discuss the potential astrobiological implications of salticles as enclosed salt‐saturated habitats that are protected from ionizing radiation and have a stable water activity.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Assessment of Nitrogen Fixation by Mungbean Genotypes in Different Soil Textures Using 15N Natural Abundance Method - Andre A. Diatta; Wade E. Thomason; Ozzie Abaye; Thomas L. Thompson; Martin L. Battaglia; Larry J. Vaughan; Mamadou Lo; Jose F. D. C. L. Filho (Journal of Soil Science and Plant Nutrition, 2020)

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Effect of carbohydrate–protein supplementation on endurance training adaptations - Abdullah F. Alghannam; Iain Templeman; Joel E. Thomas; Dawid Jedrzejewski; Samuel Griffiths; Joseph Lemon; Thomas Byers; Sue Reeves; Javier T. Gonzalez; Dylan Thompson; James Bilzon; Kostas Tsintzas; et al. (European Journal of Applied Physiology, 2020)
Purpose To examine the influence of post-exercise protein feeding upon the adaptive response to endurance exercise training. Methods In a randomised parallel group design, 25 healthy men and women completed 6 weeks of endurance exercise training by running on a treadmill for 30–60 min at 70–75% maximal oxygen uptake ( V O 2max ) 4 times/week. Participants ingested 1.6 g per kilogram of body mass (g kg BM −1 ) of carbohydrate (CHO) or an isocaloric carbohydrate–protein solution (CHO-P; 0.8 g carbohydrate kg BM −1 + 0.8 g protein kg BM −1 ) immediately and 1 h post-exercise. Expired gas, blood and muscle biopsy samples were taken at baseline and follow-up. Results Exercise training improved V O 2max in both groups ( p ≤ 0.001), but this increment was not different between groups either in absolute terms or relative to body mass (0.2 ± 0.2 L min −1 and 3.0 ± 2 mL kg −1 min −1 , respectively). No change occurred in plasma albumin concentration from baseline to follow-up with CHO-P (4.18 ± 0.18 to 4.23 ± 0.17 g dL −1 ) or CHO (4.17 ± 0.17 to 4.12 ± 0.22 g dL −1 ; interaction: p > 0.05). Mechanistic target of rapamycin (mTOR) gene expression was up-regulated in CHO-P (+ 46%; p = 0.025) relative to CHO (+ 4%) following exercise training. Conclusion Post-exercise protein supplementation up-regulated the expression of mTOR in skeletal muscle over 6 weeks of endurance exercise training. However, the magnitude of improvement in V O 2max was similar between groups.

Use of Environmental DNA to Detect Grass Carp Spawning Events - Cari-Ann Hayer; Michael F. Bayless; Amy George; Nathan Thompson; Catherine A. Richter; Duane C. Chapman (Fishes, 2020)
The timing and location of spawning events are important data for managers seeking to control invasive grass carp populations. Ichthyoplankton tows for grass carp eggs and larvae can be used to detect spawning events; however, these samples can be highly debris-laden, and are expensive and laborious to process. An alternative method, environmental DNA (eDNA) technology, has proven effective in determining the presence of aquatic species. The objectives of this project were to assess the use of eDNA collections and quantitative eDNA analysis to assess the potential spawning of grass carp in five reservoir tributaries, and to compare those results to the more traditional method of ichthyoplankton tows. Grass carp eDNA was detected in 56% of sampling occasions and was detected in all five rivers. Concentrations of grass carp eDNA were orders of magnitude higher in June, corresponding to elevated discharge and egg presence. Grass carp environmental DNA flux (copies/h) was lower when no eggs were present and was higher when velocities and discharge increased and eggs were present. There was a positive relationship between grass carp eDNA flux and egg flux. Our results support the further development of eDNA analysis as a method to detect the spawning events of grass carp or other rheophilic spawners.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Caveolin and lipid domains–close companions in managing cellular pathways - Jody V. Vykoukal; Johannes F. Fahrmann; Timothy C. Thompson (Cancer and Metastasis Reviews, 2020)

Tyre wear particles: an abundant yet widely unreported microplastic? - Lydia J. Knight; Florence N. F. Parker-Jurd; Maya Al-Sid-Cheikh; Richard C. Thompson (Environmental Science and Pollution Research, 2020)

Mid-level clouds over the Sahara in a convection-permitting regional model - Damianos F. Mantsis; Steven Sherwood; Vishal Dixit; Hugh Morrison; Greg Thompson (Climate Dynamics, 2020)

Polymeric Nanocarrier Formulations of Biologics Using Inverse Flash NanoPrecipitation - Chester E. Markwalter; Robert F. Pagels; Ava N. Hejazi; Akiva G. R. Gordon; Alexandra L. Thompson; Robert K. Prud’homme (The AAPS Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Effects of ocean climate on the length and condition of forage fish in the Gulf of Alaska - Sarah Ann Thompson; Marisol García‐Reyes; William J. Sydeman; Mayumi L. Arimitsu; Scott A. Hatch; John F. Piatt (Fisheries Oceanography, 2019)
Climatic drivers of the size and body condition of forage fish in the North Pacific are poorly known. We hypothesized that length and condition of forage fish in the Gulf of Alaska (GoA) vary in relation to ocean temperature on multiple scales. To test this hypothesis, we analyzed morphometric data for capelin ( Mallotus catervarius ) and Pacific sand lance (PSL; Ammodytes personatus ) sampled by a seabird ( Cerorhinca monocerata ) in two regions of the GoA, 1993–2016. Based on previous studies, we predicted that capelin length and body condition (Fulton's K ) would be negatively related to the Pacific Decadal Oscillation (PDO) and sea surface temperature (SST), whereas PSL length and condition would be positively related. Interannual variation in length and body condition was evaluated relative to seasonal values of ocean climate using regression. Forage fish length and condition varied interannually, between sampling regions, and were dependent on the size/age class of the fish sampled. As predicted, length and body condition of capelin (mostly age 1+) were negatively related to the PDO and SST. Relationships with ocean climate for PSL varied by size/age class: positive for putative age‐0 fish and negative for putative age‐1+ fish. We conclude that our hypothesis was supported for capelin and partially supported for PSL. This study demonstrates that ocean climate determines key morphometric characteristics of forage fish that may relate to interannual variation in the energetic value of prey, and provides an example of how seabirds can be used to obtain specimens for evaluations of potential prey quality.

Access Matting Reduces Mixedgrass Prairie Soil and Vegetation Responses to Industrial Disturbance - F. Najafi; K. A. Thompson; C. N. Carlyle; S. A. Quideau; E. W. Bork (Environmental Management, 2019)

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

Identification of a novel species of Eimeria Schneider, 1875 from the woylie, Bettongia penicillata Gray (Diprotodontia: Potoroidae) and the genetic characterisation of three Eimeria spp. from other potoroid marsupials - Amy S. Northover; Sarah Keatley; Aileen D. Elliot; Russell P. Hobbs; Rongchang Yang; Alan J. Lymbery; Stephanie S. Godfrey; Adrian F. Wayne; R. C. Andrew Thompson (Systematic Parasitology, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Behavioural response of workers to repeated intergroup encounters in the harvester ant Messor barbarus - G. Birch; M. A. Cant; F. J. Thompson (Insectes Sociaux, 2019)

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Molecular identification of Botryosphaeria dothidea as a fungal associate of the gall midge Asphondylia prosopidis on mesquite in the United States - Ikju Park; Soum Sanogo; Stephen F. Hanson; David C. Thompson (BioControl, 2019)

Geochemistry and provenance of the Turquoise Bluff Slate, northeastern Tasmania: tectonic significance - R. F. Berry; K. Goemann; J. Thompson; S. Meffre; R. Bottrill (Australian Journal of Earth Sciences, 2019)

Identification of newly settled Caribbean coral recruits by ITS-targeted single-step nested multiplex PCR - Elijah D. O’Cain; Marc E. Frischer; J. Scott Harrison; Tina L. Walters; Megan E. Thompson; Nicole D. Fogarty; Rob Ruzicka; Daniel F. Gleason (Coral Reefs, 2019)

Seabed Mining and Approaches to Governance of the Deep Seabed - Kirsten F. Thompson; Kathryn A. Miller; Duncan Currie; Paul Johnston; David Santillo (Frontiers in Marine Science, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

Comparison of two methods of determining lung de-recruitment, using the forced oscillation technique - K. Nilsen; K. Gove; F. Thien; T. Wilkinson; B. R. Thompson (European Journal of Applied Physiology, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Biogeography of pelagic food webs in the North Pacific - John F. Piatt; Mayumi L. Arimitsu; William J. Sydeman; Sarah Ann Thompson; Heather Renner; Stephani Zador; David Douglas; Scott Hatch; Arthur Kettle; Jeff Williams (Fisheries Oceanography, 2018)
The tufted puffin ( Fratercula cirrhata ) is a generalist seabird that breeds throughout the North Pacific and eats more than 75 different prey species. Using puffins as samplers, we characterized the geographic variability in pelagic food webs across the subarctic North Pacific from the composition of ~10,000 tufted puffin meals (~56,000 prey items) collected at 35 colonies in the Gulf of Alaska (GoA) and Aleutian Archipelago. Cluster analysis of diet species composition suggested three distinct forage fish communities: (i) in the northern GoA, multiple age‐classes of coastal and shelf residents such as capelin, sand lance and herring dominated the food web, (ii) in the western GoA to eastern Aleutians, the shelf community was dominated by transient age‐0 walleye pollock, and (iii) in the western Aleutians, shelf‐edge and mesopelagic forage species such as squid, lanternfish, and Atka mackerel were prevalent. Geographic patterns of abundance of capelin and sand lance in tufted puffin diets were corroborated by independent research fisheries and diets of piscivorous fish, indicating that puffin diets reflect the local abundance of forage species, not just selection of favored species. Generalized additive models showed that habitat characteristics predict, in a non‐linear fashion, forage species distribution and abundance across two large marine ecosystems. We conclude that major biogeographic patterns in forage fish distribution follow gradients in key habitat features, and puffin diets reflect those patterns.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Rapid isolation of culturable microalgae from a tropical shallow lake system - Giovana O. Fistarol; Paulo I. Hargreaves; Juline M. Walter; Tatiana V. Viana; Piter D. F. Gomes; Caio Brito Lourenço; Carlos E. Rezende; Gustavo Gregoracci; Cintia Rua; Cristiane C. Thompson; Fabiano L. Thompson; Paulo S. Salomon (Journal of Applied Phycology, 2018)

Genomic Attributes of Novel Symbiont Pseudovibrio brasiliensis sp. nov. Isolated From the Sponge Arenosclera brasiliensis - Adriana M. Fróes; Thamyres C. Freitas; Livia Vidal; Luciana R. Appolinario; Luciana Leomil; Tainá Venas; Mariana E. Campeão; Carlos J. F. Silva; Ana Paula B. Moreira; Roberto G. S. Berlinck; Fabiano L. Thompson; Cristiane C. Thompson (Frontiers in Marine Science, 2018)

An Overview of Seabed Mining Including the Current State of Development, Environmental Impacts, and Knowledge Gaps - Kathryn A. Miller; Kirsten F. Thompson; Paul Johnston; David Santillo (Frontiers in Marine Science, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Natriuretic peptide activation of extracellular regulated kinase 1/2 (ERK1/2) pathway by particulate guanylyl cyclases in GH3 somatolactotropes - Kim C. Jonas; Timothy Melrose; Iain R. Thompson; Gary F. Baxter; Victoria J. Lipscomb; Stijn J. Niessen; Charlotte Lawson; Craig A. McArdle; Mark S. Roberson; Imelda M. McGonnell; Caroline P. Wheeler-Jones; Robert C. Fowkes (Cell and Tissue Research, 2017)

Caffeine increases the velocity of rapid eye movements in unfatigued humans - Charlotte J. W. Connell; Benjamin Thompson; Jason Turuwhenua; Robert F. Hess; Nicholas Gant (Psychopharmacology, 2017)

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Increased appendicularian zooplankton alter carbon cycling under warmer more acidified ocean conditions - Monika Winder; Jean‐Marie Bouquet; J. Rafael Bermúdez; Stella A. Berger; Thomas Hansen; Jay Brandes; Andrey F. Sazhin; Jens C. Nejstgaard; Ulf Båmstedt; Hans H. Jakobsen; Jörg Dutz; Marc E. Frischer; et al. (Limnology and Oceanography, 2017)
Anthropogenic atmospheric loading of CO 2 raises concerns about combined effects of increasing ocean temperature and acidification, on biological processes. In particular, the response of appendicularian zooplankton to climate change may have significant ecosystem implications as they can alter biogeochemical cycling compared to classical copepod dominated food webs. However, the response of appendicularians to multiple climate drivers and effect on carbon cycling are still not well understood. Here, we investigated how gelatinous zooplankton (appendicularians) affect carbon cycling of marine food webs under conditions predicted by future climate scenarios. Appendicularians performed well in warmer conditions and benefited from low pH levels, which in turn altered the direction of carbon flow. Increased appendicularians removed particles from the water column that might otherwise nourish copepods by increasing carbon transport to depth from continuous discarding of filtration houses and fecal pellets. This helps to remove CO 2 from the atmosphere, and may also have fisheries implications.

Puffins reveal contrasting relationships between forage fish and ocean climate in the North Pacific - William J. Sydeman; John F. Piatt; Sarah Ann Thompson; Marisol García‐Reyes; Scott A. Hatch; Mayumi L. Arimitsu; Leslie Slater; Jeffrey C. Williams; Nora A. Rojek; Stephani G. Zador; Heather M. Renner (Fisheries Oceanography, 2017)
Long‐term studies of predator food habits (i.e., ‘predator‐based sampling’) are useful for identifying patterns of spatial and temporal variability of forage nekton in marine ecosystems. We investigated temporal changes in forage fish availability and relationships to ocean climate by analyzing diet composition of three puffin species (horned puffin Fratercula corniculata , tufted puffin Fratercula cirrhata , and rhinoceros auklet Cerorhinca monocerata ) from five sites in the North Pacific from 1978–2012. Dominant forage species included squids and hexagrammids in the western Aleutians, gadids and Pacific sand lance ( Ammodytes personatus ) in the eastern Aleutians and western Gulf of Alaska (GoA), and sand lance and capelin ( Mallotus villosus ) in the northern and eastern GoA. Interannual fluctuations in forage availability dominated variability in the western Aleutians, whereas lower‐frequency shifts in forage fish availability dominated elsewhere. We produced regional multivariate indicators of sand lance, capelin, and age‐0 gadid availability by combining data across species and sites using Principal Component Analysis, and related these indices to environmental factors including sea level pressure ( SPL ), winds, and sea surface temperature ( SST ). There was coherence in the availability of sand lance and capelin across the study area. Sand lance availability increased linearly with environmental conditions leading to warmer ocean temperatures, whereas capelin availability increased in a non‐linear manner when environmental changes led to lower ocean temperatures. Long‐term studies of puffin diet composition appear to be a promising tool for understanding the availability of these difficult‐to‐survey forage nekton in remote regions of the North Pacific.

MRI Characterization in the Acute Phase of Experimental Subarachnoid Hemorrhage - Dewei Guo; D. Andrew Wilkinson; B. Gregory Thompson; Aditya S. Pandey; Richard F Keep; Guohua Xi; Ya Hua (Translational Stroke Research, 2017)

Behavioral Plasticity in Response to Perceived Predation Risk in Breeding House Wrens - Erin E. Dorset; Scott K. Sakaluk; Charles F. Thompson (Evolutionary Biology, 2017)

Predation by New Zealand sea lions and Brown Skuas is causing the continued decline of an Eastern Rockhopper Penguin colony on Campbell Island - Kyle W. Morrison; Doug P. Armstrong; Phil F. Battley; Sarah E. Jamieson; David R. Thompson (Polar Biology, 2017)

Modeling abundance, growth, and health of the solitary coral Scolymia wellsi (Mussidae) in turbid SW Atlantic coral reefs - Ericka O. C. Coni; Camilo M. Ferreira; Pedro M. Meirelles; Rafael Menezes; Erika F. C. Santana; Ana Paula B. Moreira; Gilberto M. Amado-Filho; Beatrice P. Ferreira; Guilherme H. Pereira-Filho; Fabiano L. Thompson; Rodrigo L. Moura; Ronaldo B. Francini-Filho (Marine Biology, 2017)

Continued feeding on Diporeia by deepwater sculpin in Lake Huron - Patricia A. Thompson; Edward F. Roseman; Kevin M. Keeler; Timothy P. O’Brien; Dustin A. Bowser (Environmental Biology of Fishes, 2017)

Barriers and Strategies to Participation in Tissue Research Among African-American Men - Bettina F. Drake; Danielle Boyd; Kimberly Carter; Sarah Gehlert; Vetta Sanders Thompson (Journal of Cancer Education, 2017)

Maternal Natal Environment and Breeding Territory Predict the Condition and Sex Ratio of Offspring - E. Keith Bowers; Charles F. Thompson; Scott K. Sakaluk (Evolutionary Biology, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

An advanced white matter tract analysis in frontotemporal dementia and early-onset Alzheimer’s disease - Madelaine Daianu; Mario F. Mendez; Vatche G. Baboyan; Yan Jin; Rebecca J. Melrose; Elvira E. Jimenez; Paul M. Thompson (Brain Imaging and Behavior, 2016)

Proposal of fifteen new species of Parasynechococcus based on genomic, physiological and ecological features - F. H. Coutinho; B. E. Dutilh; C. C. Thompson; F. L. Thompson (Archives of Microbiology, 2016)

Vestibular ablation and a semicircular canal prosthesis affect postural stability during head turns - Lara A. Thompson; Csilla Haburcakova; Richard F. Lewis (Experimental Brain Research, 2016)

Spring temperatures influence selection on breeding date and the potential for phenological mismatch in a migratory bird - E. Keith Bowers; Jennifer L. Grindstaff; Sheryl Swartz Soukup; Nancy E. Drilling; Kevin P. Eckerle; Scott K. Sakaluk; Charles F. Thompson (Ecology, 2016)
Climate change has affected the seasonal phenology of a variety of taxa, including that of migratory birds and their critical food resources. However, whether climate‐induced changes in breeding phenology affect individual fitness, and how these changes might therefore influence selection on breeding date remain unresolved. Here, we use a 36‐yr dataset from a long‐term, individual‐based study of House Wrens ( Troglodytes aedon ) to test whether the timing of avian breeding seasons is associated with annual changes in temperature, which have increased to a small but significant extent locally since the onset of the study in 1980. Increasing temperature was associated with an advancement of breeding date in the population, as the onset of breeding within years was closely associated with daily spring temperatures. Warmer springs were also associated with a reduced incubation period, but reduced incubation periods were associated with a prolonged duration of nestling provisioning. Nest productivity, in terms of fledgling production, was not associated with temperature, but wetter springs reduced fledging success. Most years were characterized by selection for earlier breeding, but cool and wet years resulted in stabilizing selection on breeding date. Our results indicate that climate change and increasing spring temperatures can affect suites of life‐history traits, including selection on breeding date. Increasing temperatures may favor earlier breeding, but the extent to which the phenology of populations might advance may be constrained by reductions in fitness associated with early breeding during cool, wet years. Variability in climatic conditions will, therefore, shape the extent to which seasonal organisms can respond to changes in their environment.

The association between habitual physical activity and cigarette cravings, and influence of smokers’ characteristics in disadvantaged smokers not ready to quit - M. Haasova; F. C. Warren; T. Thompson; M. Ussher; A. H. Taylor (Psychopharmacology, 2016)

Spawn date explains variation in growth rate among families of hatchery reared Hood River steelhead (Oncorhynchus mykiss) - Neil F. Thompson; Mark R. Christie; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2016)

The combined influence of two agricultural contaminants on natural communities of phytoplankton and zooplankton - Leanne F. Baker; Joseph F. Mudge; Dean G. Thompson; Jeff E. Houlahan; Karen A. Kidd (Ecotoxicology, 2016)

Quantitative immunoenzymatic detection of viral encephalopathy and retinopathy virus (betanodavirus) in sea bass Dicentrarchus labrax - N Nuñez‐Ortiz; V Stocchi; A Toffan; F Pascoli; N Sood; F Buonocore; S Picchietti; C Papeschi; A R Taddei; K D Thompson; G Scapigliati (Journal of Fish Diseases, 2016)
Viral encephalopathy and retinopathy disease caused by betanodavirus, genus of the family Nodaviridae, affects marine, wild and farmed species including sea bass, one of the most important farmed species in Europe. This work describes a reliable and sensitive indirect ELISA assay to detect betanodavirus in biological samples using a polyclonal antiserum (pAb 283) against the 283/I09 virus strain, the most common red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype in the Mediterranean area, and a capture‐based ELISA using a monoclonal antibody (mAb 4C3) specific to a common epitope present on the capsid protein. Using adsorbed, purified VER v preparation, the detection limit of indirect ELISA was 2 μg mL −1 (3 × 10 5 TCID 50 per mL), whereas for capture‐based ELISA, the sensitivity for the antigen in solution was 17 μg mL −1 (35 × 10 5 TCID 50 per mL). The capture‐based ELISA was employed to detect VER v in brain homogenates of in vivo infected sea bass and resulted positive in 22 of 32 samples, some of these with a high viral load estimates (about 1.1 × 10 8 TCID 50 per mL). The ELISA system we propose may be helpful in investigations where coupling of viral content in fish tissues with the presence of circulating VER v‐specific IgM is required, or for use in samples where PCR is difficult to perform.

Distribution of Prochlorococcus Ecotypes in the Red Sea Basin Based on Analyses of rpoC1 Sequences - Ahmed A. Shibl; Mohamed F. Haroon; David K. Ngugi; Luke R. Thompson; Ulrich Stingl (Frontiers in Marine Science, 2016)

Sustainability of Rooftop Technologies in Cold Climates: Comparative Life Cycle Assessment of White Roofs, Green Roofs, and Photovoltaic Panels - Eduard Cubi; Nicholas F. Zibin; Sarah J. Thompson; Joule Bergerson (Journal of Industrial Ecology, 2016)
Summary Sustainable building rooftop technologies, such as white roofs, green roofs, and photovoltaic(s) (PV) panels, are becoming increasingly implemented as a result of their associated environmental benefits. Studies of these rooftop technologies are often located in hot climates and do not assess their full environmental consequences. Further, current studies tend to focus on one technology and often do not evaluate the full range of technology options using a systematic framework with common assumptions and boundaries. This article evaluates the environmental performance on a life cycle basis of white roofs, green roofs, and roof‐mounted PV in the cold Canadian climate. Solar PV demonstrates the highest environmental performance in all impact categories considered (see complete list in Results section) and is the preferred option from an environmental perspective. Green roofs result in beneficial environmental impacts, although much less significant than those obtained with PV, and are the only rooftop technology that reduces both heating and cooling energy use. The environmental performance of white roofs in cold climates is strongly affected by the heating penalty (i.e., the increase in heating energy use resulting from the high solar reflectance). Although white roofs have been proven an outstanding option in warmer climates, in cold climates, net negative environmental impacts lead to white roof technology not being recommended for general applications in cold climates. A sensitivity analysis shows that the conclusions in this study provide robust insights across Canada and cold climates in general.

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Clinically effective OCD treatment prevents 5-HT1B receptor-induced repetitive behavior and striatal activation - Emily V. Ho; Summer L. Thompson; William R. Katzka; Mitra F. Sharifi; James A. Knowles; Stephanie C. Dulawa (Psychopharmacology, 2016)

Defining multiple, distinct, and shared spatiotemporal patterns of DNA replication and endoreduplication from 3D image analysis of developing maize (Zea mays L.) root tip nuclei - Hank W. Bass; Gregg G. Hoffman; Tae-Jin Lee; Emily E. Wear; Stacey R. Joseph; George C. Allen; Linda Hanley-Bowdoin; William F. Thompson (Plant Molecular Biology, 2015)

Physiological and molecular responses to an acute bout of reduced-exertion high-intensity interval training (REHIT) - R. S. Metcalfe; F. Koumanov; J. S. Ruffino; K. A. Stokes; G. D. Holman; D. Thompson; N. B. J. Vollaard (European Journal of Applied Physiology, 2015)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Field Evaluation of Transgenic Switchgrass Plants Overexpressing PvMYB4 for Reduced Biomass Recalcitrance - Holly L. Baxter; Charleson R. Poovaiah; Kelsey L. Yee; Mitra Mazarei; Miguel Rodriguez; Olivia A. Thompson; Hui Shen; Geoffrey B. Turner; Stephen R. Decker; Robert W. Sykes; Fang Chen; Mark F. Davis; et al. (BioEnergy Research, 2015)

Chromium Is Elevated in Fin Whale (Balaenoptera physalus) Skin Tissue and Is Genotoxic to Fin Whale Skin Cells - Catherine F. Wise; Sandra S. Wise; W. Douglas Thompson; Christopher Perkins; John Pierce Wise (Biological Trace Element Research, 2015)

Effects of shoreline hardening on nitrogen processing in estuarine marshes of the U.S. mid-Atlantic coast - Theresa O’Meara; Suzanne P. Thompson; Michael F. Piehler (Wetlands Ecology and Management, 2015)

Altered regional brain volumes in elderly carriers of a risk variant for drug abuse in the dopamine D2 receptor gene (DRD2) - Florence F. Roussotte; Neda Jahanshad; Derrek P. Hibar; Paul M. Thompson (Brain Imaging and Behavior, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Rare germline copy number deletions of likely functional importance are implicated in endometrial cancer predisposition - Gemma L. Moir-Meyer; John F. Pearson; Felicity Lose; Rodney J. Scott; Mark McEvoy; John Attia; Elizabeth G. Holliday; Paul D. Pharoah; Alison M. Dunning; Deborah J. Thompson; Douglas F. Easton; Amanda B. Spurdle; et al. (Human Genetics, 2015)

Population dynamics of Eastern Rockhopper Penguins on Campbell Island in relation to sea surface temperature 1942–2012: current warming hiatus pauses a long-term decline - Kyle W. Morrison; Phil F. Battley; Paul M. Sagar; David R. Thompson (Polar Biology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Sex reversal, selection against hatchery females or wild males does not explain differences in sex ratio between first generation hatchery and wild steelhead, Oncorhynchus mykiss - Neil F. Thompson; Kathleen S. Cole; Laura A. McMahon; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2015)

Neonatal body condition, immune responsiveness, and hematocrit predict longevity in a wild bird population - E. Keith Bowers; Christine J. Hodges; Anna M. Forsman; Laura A. Vogel; Brian S. Masters; Bonnie G. P. Johnson; L. Scott Johnson; Charles F. Thompson; Scott K. Sakaluk (Ecology, 2014)
Measures of body condition, immune function, and hematological health are widely used in ecological studies of vertebrate populations, predicated on the assumption that these traits are linked to fitness. However, compelling evidence that these traits actually predict long‐term survival and reproductive success among individuals in the wild is lacking. Here, we show that body condition (i.e., size‐adjusted body mass) and cutaneous immune responsiveness to phytohemagglutinin (PHA) injection among neonates positively predict recruitment and subsequent longevity in a wild, migratory population of House Wrens ( Troglodytes aedon ). However, neonates with intermediate hematocrit had the highest recruitment and longevity. Neonates with the highest PHA responsiveness and intermediate hematocrit prior to independence eventually produced the most offspring during their lifetime breeding on the study site. Importantly, the effects of PHA responsiveness and hematocrit were revealed while controlling for variation in body condition, sex, and environmental variation. Thus, our data demonstrate that body condition, cutaneous immune responsiveness, and hematocrit as a neonate are associated with individual fitness. Although hematocrit's effect is more complex than traditionally thought, our results suggest a previously underappreciated role for this trait in influencing survival in the wild.

Assessing Potato Psyllid Haplotypes in Potato Crops in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Joseph E. Munyaneza; Alexzandra F. Murphy; Silvia I. Rondon; Brandon Thompson; Alexander V. Karasev; Erik J. Wenninger; Nora Olsen; James M. Crosslin (American Journal of Potato Research, 2014)

Hydrologic Regimes Revealed Bundles and Tradeoffs Among Six Wetland Services - James M. Doherty; Jeffrey F. Miller; Stephanie G. Prellwitz; Anita M. Thompson; Steven P. Loheide; Joy B. Zedler (Ecosystems, 2014)

The Foraging Costs of Mating Effort in Male Chimpanzees (Pan troglodytes schweinfurthii) - A. V. Georgiev; A. F. Russell; M. Emery Thompson; E. Otali; M. N. Muller; R. W. Wrangham (International Journal of Primatology, 2014)

Resurrection of Mesoplodon hotaula Deraniyagala 1963: A new species of beaked whale in the tropical Indo‐Pacific - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kirsten Thompson; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; Manori Goonatilake; R. Charles Anderson; James G. Mead; Charles W. Potter; Lisa Thompson; et al. (Marine Mammal Science, 2014)
We present genetic and morphological evidence supporting the recognition of a previously synonymized species of Mesoplodon beaked whale in the tropical Indo‐Pacific, Mesoplodon hotaula . Although the new species is closely‐related to the rare ginkgo‐toothed beaked whale M. ginkgodens, we show that these two lineages can be differentiated by maternally (mitochondrial DNA ), biparentally (autosomal), and paternally (Y chromosome) inherited DNA sequences, as well as by morphological features. The reciprocal monophyly of the mt DNA genealogies and the largely parapatric distribution of these lineages is consistent with reproductive isolation. The new lineage is currently known from at least seven specimens: Sri Lanka (1), Gilbert Islands, Republic of Kiribati (1+), Palmyra Atoll, Northern Line Islands, U.S.A. (3), Maldives (1), and Seychelles (1). The type specimen (Sri Lanka) was described as a new species, M. hotaula , in 1963, but later synonymized with M. ginkgodens . This discovery brings the total number of Mesoplodon species to 15, making it, by far, the most speciose yet least known genus of cetaceans.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Neuroimaging and genetic risk for Alzheimer’s disease and addiction-related degenerative brain disorders - Florence F. Roussotte; Madelaine Daianu; Neda Jahanshad; Cassandra D. Leonardo; Paul M. Thompson (Brain Imaging and Behavior, 2014)

Prototype decision support system based on the VegSyst simulation model to calculate crop N and water requirements for tomato under plastic cover - M. Gallardo; R. B. Thompson; C. Giménez; F. M. Padilla; C. O. Stöckle (Irrigation Science, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Physiological modifications of seston in response to physicochemical gradients within Lake Superior - Brent J. Bellinger; Benjamin A. S. Van Mooy; James B. Cotner; Helen F. Fredricks; Claudia R. Benitez-Nelson; Jo Thompson; Anne Cotter; Michael L. Knuth; Casey M. Godwin (Limnology and Oceanography, 2014)
In September 2011, we investigated the distribution and composition of dissolved and particulate phosphorus (P) pools throughout Lake Superior, a large P‐limited freshwater ecosystem. Average seston particulate P (PP) concentrations in the deep chlorophyll maximum (DCM; 85 ± 28 nmol L −1 ) were significantly greater than in the epilimnion (63 ± 22 nmol L −1 ). In contrast, average particulate organic carbon (POC) : PP (mol : mol) ratios showed the opposite pattern (DCM = 303 : 1 vs. epilimnion = 455 : 1). Mean seston nucleic acid—P concentrations were invariant between the epilimnetic (23 ± 18 nmol L −1 ) and DCM (26 ± 18 nmol L −1 ) layers, but significantly greater concentrations of intact polar membrane—derived phospholipids were found in the DCM (6 ± 2 nmol L −1 ) relative to the epilimnion (4 ± 2 nmol L −1 ). Phospholipids were a minor proportion of PP (7–14%) and total membrane lipids ( −1 ) than in the DCM (4 ± 2 nmol L −1 ), despite low sulfate concentrations relative to marine environments. Our results demonstrate for the first time the importance of plankton producing non‐phosphorus lipids for phospholipids as a strategy for reducing cellular P inventories in lacustrine regimes.

The effect of movement kinematics on predicting the timing of observed actions - Lincoln J. Colling; William F. Thompson; John Sutton (Experimental Brain Research, 2014)

Surface antigen profiles of leukocytes and melanoma cells in lymph node metastases are associated with survival in AJCC stage III melanoma patients - Kimberley L. Kaufman; Swetlana Mactier; Nicola J. Armstrong; Duthika Mallawaaratchy; Scott N. Byrne; Lauren E. Haydu; Valerie Jakrot; John F. Thompson; Graham J. Mann; Richard A. Scolyer; Richard I. Christopherson (Clinical & Experimental Metastasis, 2014)

Kinetics of short-term carbon mineralization in roots of biofuel crops in soils - F. A. Rivas; M. A. Tabatabai; D. C. Olk; M. L. Thompson (Biology and Fertility of Soils, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Homologous and heterologous desensitization of guanylyl cyclase-B signaling in GH3 somatolactotropes - Iain R. Thompson; Samantha M. Mirczuk; Lorna Smith; Andrew J. Lessey; Bigboy Simbi; Andrew Sunters; Gary F. Baxter; Victoria J. Lipscomb; Imelda M. McGonnell; Caroline P. Wheeler-Jones; Abir Mukherjee; Mark S. Roberson; et al. (Cell and Tissue Research, 2014)

Effects of ocean acidification, temperature and nutrient regimes on the appendicularian Oikopleura dioica: a mesocosm study - Christofer Troedsson; Jean-Marie Bouquet; Carla M. Lobon; Aliona Novac; Jens C. Nejstgaard; Sam Dupont; Suncica Bosak; Hans H. Jakobsen; Nadezda Romanova; Lene M. Pankoke; Alejandro Isla; Jörg Dutz; et al. (Marine Biology, 2013)

The InSiGHT database: utilizing 100 years of insights into Lynch Syndrome - J. P. Plazzer; R. H. Sijmons; M. O. Woods; P. Peltomäki; B. Thompson; J. T. Den Dunnen; F. Macrae (Familial Cancer, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Assessing Nitrogen Dynamics Throughout the Estuarine Landscape - Ashley R. Smyth; Suzanne P. Thompson; Kaylyn N. Siporin; Wayne S. Gardner; Mark J. McCarthy; Michael F. Piehler (Estuaries and Coasts, 2013)

Erratum to: An exploratory analysis of common genetic variants in the vitamin D pathway including genome-wide associated variants in relation to glioma risk and outcome - Gabriella M. Anic; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; James E. Browning; Melissa H. Madden; F. Reed Murtagh; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2012)

An exploratory analysis of common genetic variants in the vitamin D pathway including genome-wide associated variants in relation to glioma risk and outcome - Gabriella M. Anic; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; James E. Browning; Melissa H. Madden; F. Reed Murtagh; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2012)

Reproductive allocation in female house wrens is not influenced by experimentally altered male attractiveness - Susan C. Grana; Scott K. Sakaluk; Rachel M. Bowden; Melissa A. Doellman; Laura A. Vogel; Charles F. Thompson (Behavioral Ecology and Sociobiology, 2012)

Methods for Studying the Ecological Physiology of Feeding in Free-Ranging Howlers (Alouatta palliata) at La Pacifica, Costa Rica - Christopher J. Vinyard; Kenneth E. Glander; Mark F. Teaford; Cynthia L. Thompson; Max Deffenbaugh; Susan H. Williams (International Journal of Primatology, 2012)

Optimizing Hippocampal Segmentation in Infants Utilizing MRI Post-Acquisition Processing - Deanne K. Thompson; Zohra M. Ahmadzai; Stephen J. Wood; Terrie E. Inder; Simon K. Warfield; Lex W. Doyle; Gary F. Egan (Neuroinformatics, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Glucuronidation and Methylation of Procyanidin Dimers B2 and 3,3″-Di-O-Galloyl-B2 and Corresponding Monomers Epicatechin and 3-O-Galloyl-Epicatechin in Mouse Liver - Suraj P. Shrestha; John A. Thompson; Michael F. Wempe; Mallikarjuna Gu; Rajesh Agarwal; Chapla Agarwal (Pharmaceutical Research, 2012)

Continuation tapping to triggered melodies: motor resonance effects of melodic motion - Paolo Ammirante; William F. Thompson (Experimental Brain Research, 2012)

Studies on the effect of temperature and pH on the inactivation of fish viral and bacterial pathogens - P F Dixon; D A Smail; M Algoët; T S Hastings; A Bayley; H Byrne; M Dodge; A Garden; C Joiner; E Roberts; D Verner‐Jeffreys; F Thompson (Journal of Fish Diseases, 2012)
Disposal of fish by‐products in the European Community must comply with Regulation (EC) No 1069/2009 which categorizes animal by‐products according to risk, and specifies methods of disposal of by‐products according to that risk. There is provision under the regulation for composting or ensiling to be used for by‐products from aquatic animals. Biosecurity considerations require knowledge of the parameters of time and temperature, or time and pH, required to inactivate any fish pathogens that may be present. To provide those data, we undertook laboratory studies on the inactivation of a number of fish pathogenic viruses and bacteria at 60 °C, pH 4.0 and pH 12.0 as a preliminary to conducting subsequent trials with the most resistant viruses and bacteria in fish tissues. The most resistant bacterium to 60 °C, pH 4.0 as well as pH 12.0 was Lactococcus garvieae . Its concentration was reduced to the level of sensitivity of the test after 24–48 h exposure to 60 °C, but it survived for at least 7 days at pH 4.0 and 14 days at pH 12.0. The most resistant virus to 60 °C was infectious pancreatic necrosis virus, and to pH 12.0 was infectious salmon anaemia virus. The majority of the viruses tested survived exposure to pH 4.0 for up to 28 days. The results suggest that the process of acid ensiling alone is not an effective method for the inactivation of many viral and bacterial pathogens, and fish by‐products would need further treatment by a method approved under the regulation following ensiling, whereas alkaline or heat treatment are likely to provide an increased degree of biosecurity for on‐farm processing of mortalities.

Nitrogen deposition enhances moss growth, but leads to an overall decline in habitat condition of mountain moss‐sedge heath - Heather F. Armitage; Andrea J. Britton; René van der Wal; Imogen S. K. Pearce; Des B. A. Thompson; Sarah J. Woodin (Global Change Biology, 2012)
Ecosystems are subject to multiple, natural and anthropogenic environmental influences, including nitrogen ( N ) deposition, land use and climate. Assessment of the relative importance of these influences on biodiversity and ecosystem functioning is crucial for guiding policy and management decisions to mitigate global change; yet, few studies consider multiple drivers. In the UK , ongoing loss of the internationally important arctic/alpine moss‐sedge community, R acomitrium heath, has been linked to elevated N deposition, high grazing pressures and their combination; however, the relative importance of these drivers remains unclear. We used environmental gradients across the habitat's E uropean distribution ( UK , F aroes, N orway and I celand) to investigate the relative impact of N deposition and grazing pressure, as well as climate, on the condition of the dominant moss species, R acomitrium lanuginosum . Key variables including tissue chemistry, growth and cover were measured at 36 sites, and multiple linear regressions were used to examine the relative importance of the drivers across sites. Our results clearly show that regional variation in the condition of R . lanuginosum across E urope is primarily associated with the impacts of N deposition, with climate (air temperature) and grazing pressure playing secondary roles. In contrast to previous experimental studies, we found moss growth to be stimulated by elevated N deposition; this apparent discrepancy may result from the use of artificially high N concentrations in many experiments. Despite increased growth rates, we found that moss mat depth and cover declined in response to N deposition. Our results suggest that this is due to increased decomposition of material in the moss mat, which ultimately leads to loss of moss cover and habitat degradation. This study clearly demonstrates both the key role of N deposition in degradation of R acomitrium heath and the importance of observational studies along natural gradients for testing predictions from experimental studies in the real world.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

A review of the evolution of viviparity in squamate reptiles: the past, present and future role of molecular biology and genomics - Bridget F. Murphy; Michael B. Thompson (Journal of Comparative Physiology B, 2011)

Dating Palaeolithic sites in southwestern Crete, Greece - Thomas F. Strasser; Curtis Runnels; Karl Wegmann; Eleni Panagopoulou; Floyd Mccoy; Chad Digregorio; Panagiotis Karkanas; Nick Thompson (Journal of Quaternary Science, 2011)
Discussions of dispersals of early hominins from Africa assume that Southwest Asia and the Arabian Peninsula were the primary passageways for migrations to Eurasia. The Mediterranean is usually viewed as a barrier to early hominin movements because pre‐ sapiens hominins were thought to lack the technical means or the cognitive skills to construct boats. The discovery of early Palaeolithic artefacts in an archaeological survey on the Greek island of Crete challenges this view. Here we show that Palaeolithic artefacts in the Plakias region in southwestern Crete are associated with geological contexts that can be dated to the late Middle or early Late Pleistocene. Because Crete has been separated from the mainland throughout the Pleistocene, the presence of Pleistocene age artefacts there suggests that early hominins were able to cross open water. Copyright © 2011 John Wiley & Sons, Ltd.

DNA methylation changes in murine breast adenocarcinomas allow the identification of candidate genes for human breast carcinogenesis - Deanna Acosta; Masako Suzuki; Diana Connolly; Reid F. Thompson; Melissa J. Fazzari; John M. Greally; Cristina Montagna (Mammalian Genome, 2011)

AKT1 polymorphisms are associated with risk for metabolic syndrome - Joseph M. Devaney; Heather Gordish-Dressman; Brennan T. Harmon; Margaret K. Bradbury; Stephanie A. Devaney; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Thomas B. Price; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; et al. (Human Genetics, 2011)

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2011)

A role for delta opioid receptors in the central nucleus of the amygdala in anxiety-like behaviors - Jovita F. Randall-Thompson; Karen A. Pescatore; Ellen M. Unterwald (Psychopharmacology, 2010)

Retention of mutualism in a geographically diverging interaction - John N. Thompson; Anna‐Liisa Laine; Jill F. Thompson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1368–1377 Abstract A current challenge in coevolutionary biology is to understand how interactions between pairs of species change as they diversify into multispecific interactions. We tested whether the previously demonstrated pairwise mutualism between the widespread pollinating floral parasite Greya politella and its Lithophragma hostplants is ecologically enhanced or diminished in a region in which another Greya species, Greya obscura , uses the same host, Lithophragma cymbalaria . Field surveys and experimental trials showed that pollination efficacy by G. politella was more than an order of magnitude higher than by G. obscura , but G. politella abundance varied greatly between years. Greya obscura had a strongly positive effect on seed set in a year when G. politella densities were exceptionally low. Our results suggest that the coevolving mutualism between Greya and Lithophragma has potentially been enhanced rather than diminished as this interaction has diversified in the number of pollinating Greya species.

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

A polymorphism near IGF1 is associated with body composition and muscle function in women from the Health, Aging, and Body Composition Study - Matthew C. Kostek; Joseph M. Devaney; Heather Gordish-Dressman; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; Linda S. Pescatello; Paul S. Visich; Robert F. Zoeller; et al. (European Journal of Applied Physiology, 2010)

Placental calcium provision in a lizard with prolonged oviductal egg retention - Brent J. Linville; James R. Stewart; Tom W. Ecay; Jacquie F. Herbert; Scott L. Parker; Michael B. Thompson (Journal of Comparative Physiology B, 2010)

The impact of climate-induced distributional changes on the validity of biological water quality metrics - Christopher Hassall; David J. Thompson; Ian F. Harvey (Environmental Monitoring and Assessment, 2010)

Reproductive timing and patterns of development for the damselfly Coenagrion puella in the field - Chris D. Lowe; Ian F. Harvey; Phillip C. Watts; David J. Thompson (Ecology, 2009)
By a combination of detailed behavioral observations and molecular genetic approaches we have assessed development time, timing of first maturity, and the extent of genetic structure through the flying season in a wild population of the damselfly Coenagrion puella in England. This work provides the first estimate of development time (egg to mature adult) in the field based on individual damselflies. Development time was significantly longer for females than males. In contrast to reported laboratory studies, there was no difference in development times between different female color morphs. Development time ranged between 347 and 396 days and was negatively correlated with egg‐laying date. As a result eggs laid early in one season reach adult maturity relatively late in the next; concurrently individuals developing from eggs laid late mature relatively early. We speculate that this pattern of development is a direct physiological response to seasonal environmental variation and results in reproductive synchrony within a population. Size, specifically hind wing length, declined with development time in males, but not in females. In one of the two years of the study there was evidence for weak clustering of related individuals during the reproductive season. This appeared to be the result of developmental synchronization within families: variance in timing of maturation was smaller in full‐sib families than in half‐sib families or randomly assigned unrelated groups.

Guidelines for the treatment of marine mammals in field research - N. J. Gales; W. D. Bowen; D. W. Johnston; K. M. Kovacs; C. L. Littnan; W. F. Perrin; J. E. Reynolds; P. M. Thompson (Marine Mammal Science, 2009)

Influence of beach morphodynamics on the bivalve Donax hanleyanus and Mesodesma mactroides populations in Argentina - Gustavo A. Thompson; Mariana F. Sánchez De Bock (Marine Ecology, 2009)
Five exposed microtidal sandy beaches of North‐eastern Buenos Aires (Argentina) were analysed to evaluate the influence of coastal dynamics on the abundance of the intertidal clams Donax hanleyanus and Mesodesma mactroides over a 1‐year period. The physical characterisation of each beach was performed using 15 environmental variables and six morphodynamic indices. The population densities of both clam species were estimated by the number of individuals per strip‐transect. Analysis of similarities revealed a significant multivariate environmental difference among beaches, which could be aggregated into a northern and a southern group. The former group was characterised by an intermediate morphodynamic state and by having, in general, high density values for both clam species. The latter was composed of beaches with an intermediate reflective state and showed, in general, low density values. Beach Index and Area showed the lowest temporal variation. Total density values, as well as density values of recruits and adults of D. hanleyanus and M. mactroides did not follow a north–south latitudinal gradient. Spatial and temporal fluctuations of density values were best explained by changes in individual physical variables rather than by changes in composite indices.

Detection and identification of aquatic mycobacteria in formalin‐fixed, paraffin‐embedded fish tissues - F Pourahmad; K D Thompson; A Adams; R H Richards (Journal of Fish Diseases, 2009)
The isolation of mycobacteria from field samples is problematic, and isolation of the bacterium is sometimes not even attempted. The detection of mycobacteria through traditional histology using formalin‐fixed, paraffin‐embedded (FFPE) tissues is neither sensitive nor specific. However, detection of mycobacterial DNA from FFPE specimens, suspected of being infected with mammalian mycobacteriosis, is a routine clinical procedure. In the present study, a polymerase chain reaction (PCR)‐based method was used to detect and identify mycobacteria in FFPE specimens sampled from fish suspected of being infected with fish mycobacteriosis. A total of 45 fish tissue samples, comprising of 12 tissue samples obtained from experimentally infected fish and the remainder from fish naturally infected with mycobacteria, were analysed using a PCR protocol which amplifies a fragment of the mycobacterial 65 kDa heat‐shock protein ( hsp65 ) gene. PCR‐restriction enzyme analysis and/or sequencing were employed to further analyse the PCR amplicons. The PCR results were compared with those obtained by histology and culture. Mycobacterial DNA was detected in 34 of the 45 samples examined, of which 16 samples (47%) showed granulomatous reactions on histological examination. Using histology as the gold standard, no false‐negative PCR results were obtained. Also, considering the presence or absence of granulomas as a diagnostic criterion, the sensitivity and specificity of PCR in 42 of the FFPE tissues were 16/16 (100%) and 8/26 (∼30.8%), respectively. Corresponding microbiological cultures were available for 15 cases, of which 13 were pure Mycobacterium cultures. Of these, 13 were PCR positive (100% sensitivity and 50% specificity). The PCR‐based methods used here proved sensitive, specific and rapid for the detection of mycobacteria in routinely processed paraffin wax‐embedded and formalin‐fixed histological samples, and the results of the study suggest that this method has potential use in retrospective epidemiological studies.

Environmental characteristics, landscape history and pressures on three coastal lagoons in the Southern Mediterranean Region: Merja Zerga (Morocco), Ghar El Melh (Tunisia) and Lake Manzala (Egypt) - F. Ayache; J. R. Thompson; R. J. Flower; A. Boujarra; F. Rouatbi; H. Makina (Hydrobiologia, 2009)

Environmental influences on the qualitative and quantitative composition of phytoplankton and zooplankton in North African coastal lagoons - M. Ramdani; N. Elkhiati; R. J. Flower; J. R. Thompson; L. Chouba; M. M. Kraiem; F. Ayache; M. H. Ahmed (Hydrobiologia, 2009)

Application of remote sensing to site characterisation and environmental change analysis of North African coastal lagoons - M. H. Ahmed; B. M. El Leithy; J. R. Thompson; R. J. Flower; M. Ramdani; F. Ayache; S. M. Hassan (Hydrobiologia, 2009)

Sediment distribution and accumulation in lagoons of the Southern Mediterranean Region (the MELMARINA Project) with special reference to environmental change and aquatic ecosystems - R. J. Flower; P. G. Appleby; J. R. Thompson; M. H. Ahmed; M. Ramdani; L. Chouba; N. Rose; R. Rochester; F. Ayache; M. M. Kraiem; N. Elkhiati; S. El Kafrawy; et al. (Hydrobiologia, 2009)

Hydrological characteristics of three North African coastal lagoons: insights from the MELMARINA project - J. R. Thompson; R. J. Flower; M. Ramdani; F. Ayache; M. H. Ahmed; E. K. Rasmussen; O. S. Petersen (Hydrobiologia, 2009)

Model analyses of the future water quality of the eutrophicated Ghar El Melh lagoon (Northern Tunisia) - E. Kock Rasmussen; O. S. Petersen; J. R. Thompson; R. J. Flower; F. Ayache; M. Kraiem; L. Chouba (Hydrobiologia, 2009)

Simultaneous excision of two transgene flanking sequences and resolution of complex integration loci - Sandeep Kumar; William F. Thompson (Plant Molecular Biology, 2009)

Body rate decoupling using haltere mid-stroke measurements for inertial flight stabilization in Diptera - R. A. Thompson; M. F. Wehling; J. H. Evers; W. E. Dixon (Journal of Comparative Physiology A, 2009)

Telemetry System for Assessing Jaw-Muscle Function in Free-ranging Primates - Susan H. Williams; Christopher J. Vinyard; Kenneth E. Glander; Max Deffenbaugh; Mark F. Teaford; Cynthia L. Thompson (International Journal of Primatology, 2008)

The Potential for New Understandings of Normal and Abnormal Cognition by Integration of Neuroimaging and Behavioral Data: Not an Exercise in Carrying Coals to Newcastle - P. T. Michie; T. W. Budd; W. R. Fulham; M. E. Hughes; S. Jamadar; P. Johnston; F. Karayanidis; N. Matthews; P. E. Rasser; U. Schall; P. M. Thompson; J. Todd; et al. (Brain Imaging and Behavior, 2008)

Evaluation of the INNO‐LiPA mycobacteria v2 assay for identification of aquatic mycobacteria - F Pourahmad; K D Thompson; J B Taggart; A Adams; R H Richards (Journal of Fish Diseases, 2008)
Fifty‐seven isolates of mycobacteria comprising 10 reference strains, 47 field isolates and one non‐ Mycobacterium isolate were screened using commercial INNO‐LiPA v2 assay kits. All mycobacteria isolates tested hybridized with the Mycobacterium genus probe on the LiPA strip. All M. marinum , M. fortuitum and M. chelonae reference and field strains and three out of the four M. gordonae isolates hybridized to their corresponding species‐ or complex‐specific probes. Two cultures (a type strain and a field isolate) yielded mixed growth of two mycobacterial species, i.e. M. chelonae and M. fortuitum. A Mycobacterium isolate from one of these cultures was subsequently purified and correctly identified with the kit. However, sequence analysis of the 16S–23S rRNA internal transcribed spacer (ITS) region of various mycobacteria isolates revealed a misidentification of M. shottsii and M. pseudoshottsii with the kit because these isolates reacted with the M. marinum / M. ulcerans probe. Moreover, nine of the 13 field isolates presumed to be M. fortuitum from the results of the kit had closer ITS sequence homology with M. conceptionense , a species which, to our knowledge, has never been reported in fish. These findings highlight the need to redesign the M. fortuitum – M. peregrinum probe included in the INNO‐LiPA assay and to introduce additional complex‐specific probes into the kit. Nevertheless, the kit proved to be a rapid and reliable method for identifying mycobacteria in the aquatic environment and would be particularly useful in laboratories without sequencing facilities.

Allometric scaling of isometric biceps strength in adult females and the effect of body mass index - Robert F. Zoeller; Eric D. Ryan; Heather Gordish-Dressman; Thomas B. Price; Richard L. Seip; Theodore J. Angelopoulos; Niall M. Moyna; Paul M. Gordon; Paul D. Thompson; Eric P. Hoffman (European Journal of Applied Physiology, 2008)

Female house wrens ( Troglodytes aedon ) increase the size, but not immunocompetence, of their offspring through extra‐pair mating - ANNA M. FORSMAN; LAURA A. VOGEL; SCOTT K. SAKALUK; BONNIE G. JOHNSON; BRIAN S. MASTERS; L. SCOTT JOHNSON; CHARLES F. THOMPSON (Molecular Ecology, 2008)
House wrens are typically socially monogamous, but frequently engage in extra‐pair matings leading to multisired broods. Because females do not appear to acquire direct material benefits from their extra‐pair mates, we tested the hypothesis that female house wrens derive indirect genetic benefits, such as enhanced immunocompetence (cutaneous immune activity, humoral immunity, and plasma bactericidal activity) and condition (size and haematoserological traits) for their offspring, by mating polyandrously. We predicted that extra‐pair young (EPY) should show greater immune responsiveness and better body condition than their within‐pair maternal half‐siblings (WPY). Contrary to our prediction, WPY had higher cutaneous immune activity than their EPY brood‐mates in two of three years, and EPY and WPY did not differ in measures of innate and humoral immunity. WPY also had higher albumin to γ‐globulin ratios than EPY; however, they were not in better condition based on other measures. EPY had consistently longer tarsi (a measure of long‐bone size) than their WPY half‐siblings, suggesting that females engage in extra‐pair copulations with larger males. The benefits of large structural size in the study population is unknown, but based on evidence from other passerines, we suggest that structural size may be an important fitness‐related trait in house wrens. We conclude that our results are not consistent with the hypothesis that females gain immune‐related benefits for their offspring by engaging in extra‐pair matings. Further study of the fitness consequences of differences in tarsus length is needed to determine whether females acquire size‐related benefits for their offspring from extra‐pair mates.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Strong genetic divergence indicates that congeneric damselflies Coenagrion puella and C. pulchellum (Odonata: Zygoptera: Coenagrionidae) do not hybridise - Chris D. Lowe; Ian F. Harvey; David J. Thompson; Phillip C. Watts (Hydrobiologia, 2008)

Impairment of movement-associated brain deactivation in multiple sclerosis: further evidence for a functional pathology of interhemispheric neuronal inhibition - S. C. Manson; C. Wegner; M. Filippi; F. Barkhof; C. Beckmann; O. Ciccarelli; N. De Stefano; Christian Enzinger; F. Fazekas; F. Agosta; A. Gass; J. Hirsch; et al. (Experimental Brain Research, 2008)

An inhibitor of methionine aminopeptidase type-2, PPI-2458, ameliorates the pathophysiological disease processes of rheumatoid arthritis - D. D. Lazarus; E. G. Doyle; S. G. Bernier; A. B. Rogers; M. T. Labenski; J. D. Wakefield; R. M. Karp; E. J. Clark; J. Lorusso; J. G. Hoyt; C. D. Thompson; G. Hannig; et al. (Inflammation Research, 2008)

Do age and baseline LDL cholesterol levels determine the effect of regular exercise on plasma lipoprotein cholesterol and apolipoprotein B levels? - Theodore J. Angelopoulos; Stephen A. Sivo; George A. Kyriazis; Jonathan D. Caplan; Robert F. Zoeller; Joshua Lowndes; Richard L. Seip; Paul D. Thompson (European Journal of Applied Physiology, 2007)

Distribution of cells expressing Jun and Fos proteins and synthesizing DNA in the adrenal cortex of hypophysectomized rats: regulation by ACTH and FGF2 - Thompson Eusébio Pavan Torres; Claudimara F. P. Lotfi (Cell and Tissue Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mapping Melanoma Lymphoscintigraphy Data onto a 3D Anatomically Based Model - Hayley M. Reynolds; P. Rod Dunbar; Roger F. Uren; John F. Thompson; Nicolas P. Smith (Annals of Biomedical Engineering, 2007)

History of diabetes mellitus and subsequent prostate cancer risk in the NIH-AARP Diet and Health Study - Brook A. Calton; Shih Chen Chang; Margaret E. Wright; Victor Kipnis; Karla Lawson; Frances E. Thompson; Amy F. Subar; Traci Mouw; David S. Campbell; Paul Hurwitz; Albert Hollenbeck; Arthur Schatzkin; et al. (Cancer Causes & Control, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)
Responses of biota to climate change take a number of forms including distributional shifts, behavioural changes and life history changes. This study examined an extensive set of biological records to investigate changes in the timing of life history transitions (specifically emergence) in British Odonata between 1960 and 2004. The results show that there has been a significant, consistent advance in phenology in the taxon as a whole over the period of warming that is mediated by life history traits. British odonates significantly advanced the leading edge (first quartile date) of the flight period by a mean of 1.51 ±0.060 (SEM, n =17) days per decade or 3.08±1.16 (SEM, n =17) days per degree rise in temperature when phylogeny is controlled for. This study represents the first review of changes in odonate phenology in relation to climate change. The results suggest that the damped temperature oscillations experienced by aquatic organisms compared with terrestrial organisms are sufficient to evoke phenological responses similar to those of purely terrestrial taxa.

Immunohistochemical Jun/Fos protein localization and DNA synthesis in rat adrenal cortex after treatment with ACTH or FGF2 - Rozana B. F. Baccaro; Pedro O. R. Mendonça; Thompson E. P. Torres; Claudimara F. P. Lotfi (Cell and Tissue Research, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)

Does cigarette smoking increase plasma urotensin II concentrations? - S. J. Gold; J. P. Thompson; J. P. Williams; E. E. F. Helm; J. Sadler; W. Song; L. L. Ng; D. G. Lambert (European Journal of Clinical Pharmacology, 2007)

Hurricanes 2004: An overview of their characteristics and coastal change - Asbury H. Sallenger; Hilary F. Stockdon; Laura Fauver; Mark Hansen; David Thompson; C. Wayne Wright; Jeff Lillycrop (Estuaries and Coasts, 2006)

An improved RT-PCR method for the detection of killer-cell immunoglobulin-like receptor (KIR) transcripts - A. Thompson; A. R. van der Slik; F. Koning; J. van Bergen (Immunogenetics, 2006)

Creatine supplementation does not enhance submaximal aerobic training adaptations in healthy young men and women - T. F. Reardon; P. A. Ruell; M. A. Fiatarone Singh; C. H. Thompson; K. B. Rooney (European Journal of Applied Physiology, 2006)

Diet of Pacific sleeper shark, a potential Steller sea lion predator, in the north‐east Pacific Ocean - M. F. Sigler; L. B. Hulbert; C. R. Lunsford; N. H. Thompson; K. Burek; G. O’Corry‐Crowe; A. C. Hirons (Journal of Fish Biology, 2006)
Pacific sleeper sharks Somniosus pacificus were captured near Steller sea lion Eumetopias jubatus rookeries during the period when Steller sea lion pups are most vulnerable to Pacific sleeper shark predation (first water entrance and weaning). Analysis of stomach contents revealed that teleosts were the dominant prey in August and cephalopods were the dominant prey in May ( n = 198). Marine mammals were found in 15% of stomachs regardless of season, but no Steller sea lion tissues were detected. Molecular genetic analysis identified grey whale Eschrichtius robustus and harbour seal Phoca vitulina remains in some Pacific sleeper shark stomachs. Most mammals were cetacean and at least 70% of the cetaceans were probably scavenged. Although Pacific sleeper shark and Steller sea lion ranges overlapped, so predation could potentially occur, the diet study suggested that predation on Steller sea lions is unlikely, at least when pups first enter the water or during weaning. Harbour seals were infrequent prey and may have been consumed alive. Pacific sleeper sharks consume fast‐swimming prey like Pacific salmon Oncorhynchus sp., most likely live animals rather than scavenged animals. Pacific sleeper sharks appeared to be opportunistic consumers of the available prey and carrion, feeding both on the bottom and in the water column, and their diet shifted to teleosts and cetacean carrion as the fish grew larger.

Net Carbon Exchange Across the Arctic Tundra-Boreal Forest Transition in Alaska 1981–2000 - C. C. Thompson; A. D. McGuire; J. S. Clein; F. S. Chapin; J. Beringer (Mitigation and Adaptation Strategies for Global Change, 2006)

Quantifying Damage, Saturation and Anisotropy in Cracked Rocks by Inverting Elastic Wave Velocities - Alexandre Schubnel; Philip M. Benson; Ben D. Thompson; Jim F. Hazzard; R. Paul Young (Pure and Applied Geophysics, 2006)

Physiological roles for ecto-5’-nucleotidase (CD73) - Sean P. Colgan; Holger K. Eltzschig; Tobias Eckle; Linda F. Thompson (Purinergic Signalling, 2006)

Dispersal and genetic structure in the American marten, Martes americana - T. BROQUET; C. A. JOHNSON; E. PETIT; I. THOMPSON; F. BUREL; J. M. FRYXELL (Molecular Ecology, 2006)
Natal dispersal in a vagile carnivore, the American marten ( Martes americana ), was studied by comparing radio‐tracking data and microsatellite genetic structure in two populations occupying contrasting habitats. The genetic differentiation determined among groups of individuals using F ST indices appeared to be weak in both landscapes, and showed no increase with geographical distance. Genetic structure investigated using pairwise genetic distances between individuals conversely showed a pattern of isolation by distance (IBD), but only in the population occurring in a homogeneous high‐quality habitat, therefore showing the advantage of individual‐based analyses in detecting within‐population processes and local landscape effects. The telemetry study of juveniles revealed a leptokurtic distribution of dispersal distances in both populations, and estimates of the mean squared parent–offspring axial distance (σ2) inferred both from the genetic pattern of IBD and from the radio‐tracking survey showed that most juveniles make little contribution to gene flow.

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

A trichloroacetic acid-acetone method greatly reduces infrared autofluorescence of protein extracts from plant tissue - Randall W. Shultz; Sharon B. Settlage; Linda Hanley-Bowdoin; William F. Thompson (Plant Molecular Biology Reporter, 2005)

Identifying brain regions for integrative sensorimotor processing with ankle movements - O. Ciccarelli; A. T. Toosy; J. F. Marsden; C. M. Wheeler-Kingshott; C. Sahyoun; P. M. Matthews; D. H. Miller; A. J. Thompson (Experimental Brain Research, 2005)

Participation and Conflict: Lessons Learned From Community Forestry - Jan R. Thompson; William F. Elmendorf; Maureen H. McDonough; Lisa L. Burban (Journal of Forestry, 2005)

Matrix attachment regions increase the efficiency and stability of RNA-mediated resistance to Tomato Spotted Wilt Virus in transgenic tobacco - Jennifer S. Levin; William F. Thompson; Alex S. Csinos; Michael G. Stephenson; Arthur K. Weissinger (Transgenic Research, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Establishment of rapidly proliferating rice cell suspension culture and its characterization by fluorescence-activated cell sorting analysis - Tae-Jin Lee; Randall W. Shultz; Linda Hanley-Bowdoin; William F. Thompson (Plant Molecular Biology Reporter, 2004)

Identification and characterization of a novel mouse prion gene allele - Sarah E. Lloyd; Simon R. Thompson; Jonathan A. Beck; Jacqueline M. Linehan; Jonathan D. F. Wadsworth; Sebastian Brandner; John Collinge; Elizabeth M. C. Fisher (Mammalian Genome, 2004)

Turtles ( Chelodina longicollis ) regulate muscle metabolic enzyme activity in response to seasonal variation in body temperature - F. Seebacher; J. Sparrow; M. B. Thompson (Journal of Comparative Physiology B, 2004)

Denitrification in a constructed wetland receiving agricultural runoff - Amy C. Poe; Michael F. Piehler; Suzanne P. Thompson; Hans W. Paerl (Wetlands, 2003)

Forest Certification of State and University Lands in North Carolina: A Comparison - F. Cubbage; S. Moore; J. Cox; L. Jervis; J. Edeburn; D. Richter; W. Boyette; M. Thompson; M. Chesnutt (Journal of Forestry, 2003)
North Carolina State University, Duke University, and the North Carolina Division of Forest Resources (DFR) recently received both Forest Stewardship Council (FSC) and Sustainable Forestry Initiative (SFI) certification for their forests. Meeting SFI standards required better environmental management systems, improved use of best management practices, and better recordkeeping but few subsequent forest management changes. FSC required about the same environmental system changes but more forest management changes to favor future natural stand management and biodiversity protection. Costs included changes in forest management and recordkeeping to achieve forest certification, inspection expenses, prescribed changes in forest management, forgone timber revenues, and more stakeholder consultation. Benefits can include an improved professional reputation, better worker safety and training, better records and processes, more active public involvement, enhanced knowledge for outreach, better environmental management systems, more holistic management, and perhaps higher timber prices or greater market access.

High-resolution simulations of global climate, part 1: present climate - P. B. Duffy; B. Govindasamy; J. P. Iorio; J. Milovich; K. R. Sperber; K. E. Taylor; M. F. Wehner; S. L. Thompson (Climate Dynamics, 2003)

Relationship between the Aerodynamic Roughness Length and the Roughness Density in Cases of Low Roughness Density* - F. Minvielle; B. Marticorena; D.A. Gillette; R.E. Lawson; R. Thompson; G. Bergametti (Environmental Fluid Mechanics, 2003)

Distribution of lipids from the yolk to the tissues during development of the water python ( Liasis fuscus ) - B. K. Speake; M. B. Thompson; F. E. Thacker; G. S. Bedford (Journal of Comparative Physiology B, 2003)

Analysis of Trans-Silencing Interactions Using Transcriptional Silencers of Varying Strength and Targets With and Without Flanking Nuclear Matrix Attachment Regions - Robert Ascenzi; Bekir Ülker; Joselyn J. Todd; Dolores A. Sowinski; Carolyn R. Schimeneck; George C. Allen; Arthur K. Weissinger; William F. Thompson (Transgenic Research, 2003)

Elevation of Transgene Expression Level by Flanking Matrix Attachment Regions (MAR) is Promoter Dependent: A Study of the Interactions of Six Promoters with the RB7 3′ MAR - S. Luke Mankin; George C. Allen; Thomas Phelan; Steven Spiker; William F. Thompson (Transgenic Research, 2003)

Cancer prevention behaviors and socioeconomic status among Hispanics and non-Hispanic Whites in a rural population in the United States - Beti Thompson; Gloria D. Coronado; Cam C. Solomon; Dale F. McClerran; Marian L. Neuhouser; Ziding Feng (Cancer Causes & Control, 2002)

High-throughput transgene copy number estimation by competitive PCR - Anton S. Callaway; Rita Abranches; Jeffery Scroggs; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 2002)

Comparison of the Toxicity of Chromium III and Chromium VI to Cyanobacteria - S. L. Thompson; F. C. R. Manning; S. M. McColl (Bulletin of Environmental Contamination and Toxicology, 2002)

Serum selenium and the risk of cervical cancer among women in the United States - Frances E. Thompson; Blossom H. Patterson; Stephanie J. Weinstein; Mary McAdams; Vickie L. Spate; Richard F. Hamman; Robert S. Levine; Katherine Mallin; Paul D. Stolley; Louise A. Brinton; J. Steven Morris; Regina G. Ziegler (Cancer Causes & Control, 2002)

The paleolimnological analysis of sediments from high mountain lake Nižné Terianske pleso in the High Tatras (Slovakia) - F. Šporka; E. Štefková; P. Bitušík; A.R. Thompson; A. Agustí-Panareda; P.G. Appleby; J.A. Grytnes; C. Kamenik; I. Krno; A. Lami; N. Rose; N.E. Shilland (Journal of Paleolimnology, 2002)

Interdisciplinary Irrigated Precision Farming Research - D. F. Heermann; J. Hoeting; S. E. Thompson; H. R. Duke; D. G. Westfall; G. W. Buchleiter; P. Westra; F. B. Peairs; K. Fleming (Precision Agriculture, 2002)

Bacillary necrosis in farmed Pangasius hypophthalmus (Sauvage) from the Mekong Delta, Vietnam - H W Ferguson; J F Turnbull; A Shinn; K Thompson; T T Dung; M Crumlish (Journal of Fish Diseases, 2001)
This is the first description of an economically important disease of intensively reared Pangasius hypophthalmus from the Mekong Delta. Major presenting signs included an increase in mortality that would not respond to treatment, and at necropsy, the presence of numerous white necrotic and pyogranulomatous foci throughout the viscera, notably in spleen, liver and kidney. Despite the confounding presence in earlier samples of numerous, primarily renal, myxosporean parasites, the common denominator amongst these and samples from eight subsequently sampled sites was the presence of moderate‐to‐large numbers of bacilli in all typical lesions. These bacteria were subsequently isolated and tentatively identified as a Bacillus sp. Pilot studies experimentally reproduced similar lesions approximately 7 days following intraperitoneal injection of the bacteria.

The role of cell differentiation state and HMG-I/Y in the expression of transgenes flanked by matrix attachment regions - Robert Ascenzi; Jennifer L. Ingram; Mara Massel; William F. Thompson; Steven Spiker; Arthur K. Weissinger (Transgenic Research, 2001)

Lifetime Reproductive Success in the Solitary Endoparasitoid, Venturia canescens - Jeffrey A. Harvey; Ian F. Harvey; David J. Thompson (Journal of Insect Behavior, 2001)

New green fluorescent protein genes for plant transformation: Intron-containing, ER-localized, and soluble-modified - S. Luke Mankin; William F. Thompson (Plant Molecular Biology Reporter, 2001)

Incidence of hybridization between Atlantic salmon, Salmo salar L., and brown trout, Salmo trutta L., in Ireland - M. A. Matthews; W. R. Poole; C. E. Thompson; J. McKillen; A. Ferguson; K. Hindar; K. F. Wheelan (Fisheries Management and Ecology, 2000)
The substantial growth of the farmed salmon industry in Europe since the 1970s has highlighted concerns regarding the genetic impact of escaped farmed salmon on wild salmonid stocks. High incidences of salmon × trout hybrids have been recorded in rivers situated near intensive salmon farming in Norway and Scotland, which may be indicative of a breakdown in reproductive isolation between salmon, Salmo salar L., and brown trout, Salmo trutta L. In the present study, salmonid fry and 0+ parr were collected from rivers in western Ireland. Allozyme and minisatellite DNA analysis were carried out on fry to determine the frequency of F1 hybrids from 10 rivers located within 38 km of salmon farms and three rivers at least 80 km from salmon farms. A total of 49 hybrids were recorded from 4135 salmonid fry (frequency = 1.2%). Mitochondrial DNA analysis showed that all hybrids arose from Atlantic salmon female × brown trout male crosses. Hybrid parr were recorded from one of the low‐risk rivers (1.0%), but were present in seven out of the 10 catchments located within 38 km of salmon farms, with frequencies ranging from 0.7% to 3.1%. The results of the present survey, which represents the first extensive record of the levels of salmon‐trout hybridization in Ireland, are discussed in relation to the continued growth of salmon farming in this country.

Use of matrix attachment regions (MARs) to minimize transgene silencing - George C. Allen; Steven Spiker; William F. Thompson (Plant Molecular Biology, 2000)

Plant Uptake Response to Metals and Nitrate in Simulated Uranium Mill Tailings Contaminated Groundwater - D. J. Baumgartner; E. P. Glenn; R. O. Kuehl; T. L. Thompson; J. F. Artiola; S. E. Menke; R. A. Saar; G. S. Moss; M. A. Algharaibeh (Water, Air, & Soil Pollution, 2000)

Amplifying dolphin mitochondrial DNA from faecal plumes - Kim M. Parsons; John F. Dallas; Diane E. Claridge; John W. Durban; Kenneth C. Balcomb Iii; Paul M. Thompson; Les R. Noble (Molecular Ecology, 1999)

Pattern and prevalence of predator damage on adult Atlantic salmon, Salmo salar L., returning to a river system in north‐east Scotland - P. M. THOMPSON; F. MACKAY (Fisheries Management and Ecology, 1999)
There remains considerable debate over the impact of predation upon Atlantic salmon, Salmo salar L., populations. The pattern and prevalence of predator damage on salmon returning to a river system in North‐east Scotland were recorded. Overall, 214 (19.5%) out of 1099 fish sampled were damaged, and 10 distinct categories of damage were identified. Measurements of scratches indicated that the damage was caused by a number of different factors. In particular, damage typically attributed to seals was suggested to be the result of attacks by odontocete cetaceans. These results highlight the multispecies nature of interactions between salmon and their predators, but suggest that damage levels may be of limited use in assessing the impact of different predators on salmonid population dynamics.

Intrusion-related gold deposits associated with tungsten-tin provinces - J. F. H. Thompson; R. H. Sillitoe; T. Baker; J. R. Lang; J. K. Mortensen (Mineralium Deposita, 1999)

The relationship between diet and breast cancer in men (United States) - Karin A. Rosenblatt; David B. Thomas; L. Margarita Jimenez; Brian Fish; Anne McTiernan; Helge Stalsberg; Annette Stemhagen; W. Douglas Thompson; Mary G. McGrea Curnen; William Satariano; Donald F. Austin; Raymond S. Greenberg; et al. (Cancer Causes & Control, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Advanced argillic lithocaps in the Bolivian tin-silver belt - R. H. Sillitoe; G. B. Steele; J. F. H. Thompson; J. R. Lang (Mineralium Deposita, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Cerebral substrates of pavlovian conditioning of discrete behavioral responses - Richard F. Thompson (Neuroscience and Behavioral Physiology, 1997)

Evolutionary conservatism of oviposition preference in a widespread polyphagous insect herbivore, Papilio zelicaon - Wayne F. Wehling; John N. Thompson (Oecologia, 1997)

Introduction of a plant intron into the luciferase gene ofPhotinus pyralis - S. Luke Mankin; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 1997)

The Accumulation of Cadmium by the Yellow Pond Lily, Nuphar variegatum , in Ontario Peatlands - E. S. Thompson; F. R. Pick; L. I. Bendell-Young (Archives of Environmental Contamination and Toxicology, 1997)

Disruption of trace conditioning of the nictitating membrane response in rabbits by central cholinergic blockade - Tsugio Kaneko; R. F. Thompson (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Organochlorine pesticide contamination in neotropical migrant passerines - R. G. Harper; J. A. Frick; A. P. Capparella; B. Borup; M. Nowak; D. Biesinger; C. F. Thompson (Archives of Environmental Contamination and Toxicology, 1996)

Computer assisted recognition and quantitation of the effects of airborne chemicals acting at different areas of the respiratory tract in mice - R. Vijayaraghavan; M. Schaper; R. Thompson; M. F. Stock; L. A. Boylstein; J. E. Luo; Y. Alarie (Archives of Toxicology, 1994)

Characteristic modifications of the breathing pattern of mice to evaluate the effects of airborne chemicals on the respiratory tract - R. Vijayaraghavan; M. Schaper; R. Thompson; M. F. Stock; Y. Alarie (Archives of Toxicology, 1993)

Control of rabbit nictitating membrane movements - Gábor T. Bartha; Richard F. Thompson (Biological Cybernetics, 1992)

Control of rabbit nictitating membrane movements - Gabor T. Bartha; Richard F. Thompson (Biological Cybernetics, 1992)

Frequency and structure of spinae on Chlorobium spp. - Joanna S. Brooke; Joel B. Thompson; Terrance J. Beveridge; Susan F. Koval (Archives of Microbiology, 1992)

Estimation of genetic variance components and heritability for tuber dormancy in diploid potatoes - P. G. Thompson; F. L. Haynes; R. H. Moll (American Journal of Potato Research, 1980)

Disappearance of dislodgable residues of five organophosphate pesticides on citrus leaves and fruit during dry and wet weather in Florida - Neal P. Thompson; Robert F. Brooks (Archives of Environmental Contamination and Toxicology, 1977)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

A multiclass, multiresidue analytical method for pesticides in water - John F. Thompson; Stuart J. Reid; Edward J. Kantor (Archives of Environmental Contamination and Toxicology, 1977)

Effects of the parental host on host selection, reproductive potential, survival and fecundity of the egg-larval parasitoid,Chelonus sp. Nearcurvimaculatus, reared onPectinophora gossypiella andPhthorimaea operculella - E. F. Legner; S. N. Thompson (BioControl, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)

The Osseo variety - F. A. Krantz; C. J. Eide; C. H. Griffith; B. C. Beresford; O. C. Turnquist; M. J. Thompson; A. G. Tolaas (American Journal of Potato Research, 1954)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)